Polarizing film, image display device, polarizing sunglasses, and method for producing polarizing film

By using a combination of polyvinyl alcohol resin and specific dyes in polarizing films and employing a precise stretching process, the problems of discoloration and thermal shrinkage of polarizing films under high temperature and high humidity environments have been solved, thereby improving the durability and optical performance of polarizing films.

CN121079622APending Publication Date: 2025-12-05NITTO DENKO CORP +1
View PDF 27 Cites 0 Cited by

Patent Information

Application Number
CN202480025251.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-13
Filing Date
2024-04-09
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing polarizing films are prone to discoloration and thermal shrinkage under high temperature and humidity conditions, which leads to a reduction in polarization characteristics and affects the performance of image display devices and polarized sunglasses.

Method used

A polarizing film containing polyvinyl alcohol resin is used, and an azo compound or its salt with a urea backbone is used as a dye. The polarizing film is manufactured through a specific stretching process, including dry stretching, dyeing and wet stretching, and the film thickness is controlled to be below 10 μm.

Benefits of technology

It effectively suppresses the discoloration and thermal shrinkage of polarizing films, improves the durability and dimensional stability of polarizing films, and enhances the optical performance of image display devices and polarized sunglasses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121079622A_ABST
    Figure CN121079622A_ABST
Patent Text Reader

Abstract

The present invention provides a polarizing film and a method for producing the polarizing film capable of suppressing decoloration and thermal shrinkage. A polarizing film according to an embodiment of the present invention is a polarizing film of 10 [mu] m or less containing a polyvinyl alcohol resin, and contains at least a first dye that is an azo compound having a ureido skeleton represented by formula (1) or a salt thereof.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a polarizing film, an image display device, a polarizing sunglass, and a method for manufacturing a polarizing film. BACKGROUND

[0002] A polarizing plate including a polarizing film is an optical member used for an image display device or a polarizing sunglass, and for example, a polarizing plate provided with a polarizing film including iodine and a polyvinyl alcohol-based resin of a dichroic substance is known (for example, Patent Literature 1). However, in the case of the polarizing plate described in Patent Literature 1, for example, there are cases in which the polarizing properties are reduced due to discoloration (fading) when left for a long time in a severe environment such as a high-temperature, high-humidity environment, or cases in which the size is changed due to thermal shrinkage.

[0003] PRIOR ART DOCUMENTS PATENT LITERATURE Patent Literature 1: International Publication No. 2010 / 100917 SUMMARY

[0004] PROBLEMS TO BE SOLVED BY THE INVENTION The present application has been made in order to solve the above-described conventional problems, and a main object thereof is to provide a polarizing film, an image display device, a polarizing sunglass, and a method for manufacturing a polarizing film, in which discoloration and thermal shrinkage are suppressed.

[0005] MEANS FOR SOLVING THE PROBLEMS [1] The polarizing film of the embodiment of the present application is a polarizing film of 10 μm or less including a polyvinyl alcohol-based resin. The polarizing film includes at least a first dye, which is an azo compound or a salt thereof having a urea skeleton represented by the following formula (1).

[0006] [Chemical Formula 1] In formula (1), Ay1and Ay2are each independently a naphthyl group which can have a substituent, or a phenyl group which can have a substituent, s and t are each independently 0 or 1, and either one of s or t is 1, and Ry1to Ry8each independently represent a hydrogen atom or a substituent: the above-mentioned phenyl group which can have a substituent refers to a phenyl group having at least one or more substituents selected from the group consisting of a sulfo group, a carboxyl group, an alkyl group having a sulfo group with a carbon number of 1 to 4, an alkyl group with a carbon number of 1 to 4, an alkoxy group with a carbon number of 1 to 4, a halogen atom, a nitro group, an amino group, an alkyl-substituted amino group with a carbon number of 1 to 4, and an alkyl-substituted acylamino group with a carbon number of 1 to 4, and the naphthyl group which can have a substituent refers to a naphthyl group which can have a substituent selected from the group consisting of a hydroxyl group, an alkoxy group having a sulfo group with a carbon number of 1 to 4, and a sulfo group: Ry1, Ry2, Ry7, and Ry8are each independently a hydrogen atom, an alkyl group with a carbon number of 1 to 4, or an alkoxy group with a carbon number of 1 to 4, and Ry3to Ry6are each independently a hydrogen atom, an alkyl group with a carbon number of 1 to 4, an alkoxy group with a carbon number of 1 to 4, or an alkoxy group having a sulfo group with a carbon number of 1 to 4.

[0007] [2] The polarizing film according to the above-mentioned [1], wherein the orientation function of the above-mentioned polyvinyl alcohol-based resin can also be 0.30 or less.

[0008] [3] The polarizing film according to the above-mentioned [1] or [2], which can further contain a second dye which is an azo compound represented by the following formula (2) or a salt thereof, and a third dye which is an azo compound represented by the following formula (3) or a salt thereof.

[0009] [Chemical Formula 2] In formula (2), Ar 11 represents a phenyl group which can have a substituent, or a naphthyl group which can have a substituent, and Rr 11 to Rr 16 each independently represent a hydrogen atom, an alkyl group with a carbon number of 1 to 4, an alkoxy group with a carbon number of 1 to 4, or an alkoxy group having a sulfo group with a carbon number of 1 to 4, and Xr 11represents an amino group which can have a substituent selected from the group consisting of an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, a benzoyl group which can have a substituent selected from the group consisting of an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, a phenylamino group which can have a substituent selected from the group consisting of an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, a benzoylamino group which can have a substituent selected from the group consisting of an alkoxy group having a carbon number of 1 to 4, a sulfo group, a hydroxyl group, an amino group, and a substituted amino group, a phenylazo group which can have a substituent selected from the group consisting of an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, or a naphthotriazole group which can have a substituent selected from the group consisting of an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, m1 and n1 each independently represent 0 or 1, in the case where m1 and n1 are 1, Rr 15 and Rr 16 each independently represent a hydrogen atom, an alkyl group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4, in the case where m1 and n1 are 0, Rr 11 and Rr 12 each independently represent a hydrogen atom, an alkyl group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4, in the case where m1 and n1 are 0, Rr

[0010] [Chemical Formula 3] In formula (3), A is the same as Ar 11 of the above formula (2), or is a substituent represented by the following general formula (4), [Chemical Formula 4] (In formula (4), A1 represents a nitro group or an amino group) R1 to R4 and R6 are the same as Rr 11 to Rr 14 X is the same as Xr 11 of the above formula (2). Also, m and n each are 0 or 1.

[0011] [4] Another aspect of the liquid crystal display device for vehicle according to the present application includes the polarizing film according to any one of the above [1] to [3].

[0012] [5] Another aspect of the image display device according to the present application includes the polarizing film according to any one of the above [1] to [3].

[0013] [6] Another aspect of the polarizing sunglasses according to the present application includes the polarizing film according to any one of the above [1] to [3].

[0014] [7] The manufacturing method of the polarizing film of the still another aspect of the present application sequentially includes a laminate production step, a dry stretching step, a dyeing step, a wet stretching step, and a drying shrinkage step. In the laminate production step, a coating liquid containing a polyvinyl alcohol-based resin is coated on a long strip-shaped thermoplastic resin substrate to produce a laminate having a polyvinyl alcohol-based resin layer and the thermoplastic resin substrate. In the dry stretching step, the laminate is stretched in the air. In the dyeing step, the polyvinyl alcohol-based resin layer after the dry stretching step is dyed with at least a first dye, which is an azo compound or a salt thereof having a urea-based skeleton represented by the above formula (1). In the wet stretching step, the polyvinyl alcohol-based resin layer after the dyeing step is stretched in a stretching bath. In the drying shrinkage step, the polyvinyl alcohol-based resin layer after the wet stretching step is conveyed along a long direction while being shrunk in a width direction orthogonal to the long direction, so that the thickness is adjusted to 10 μm or less.

[0015] [8] The manufacturing method of the polarizing film according to the above [7], wherein the stretching ratio in the dry stretching can be 2.1 times or more, and the stretching ratio in the wet stretching can be 2.0 times or less.

[0016] Effects of Invention According to the embodiment of the present application, a polarizing film, an image display device, and a polarized sunglass in which discoloration and heat shrinkage can be suppressed can be realized. BRIEF DESCRIPTION OF DRAWINGS

[0017] Figure 1 is a schematic cross-sectional view of an optical laminate including a polarizing film of one embodiment of the present application.

[0018] Figure 2 is a schematic cross-sectional view of an optical laminate including a polarizing film of another embodiment of the present application.

[0019] Figure 3 is a schematic cross-sectional view of an optical laminate including a polarizing film of still another embodiment of the present application. DETAILED DESCRIPTION

[0020] Hereinafter, representative embodiments of the present application will be described, but the present application is not limited to these embodiments. Furthermore, in order to make the description more clear, the width, thickness, shape, and the like of each portion are schematically shown in the drawings in comparison with the embodiments, but these are one example and do not limit the explanation of the present application.

[0021] (Definition of Terms and Symbols) The definition of terms and symbols in this specification is described below.

[0022] (1) Refractive Index (nx, ny, nz) "nx" is the refractive index in the direction in which the refractive index in the plane becomes the largest (i.e., the slow axis direction), "ny" is the refractive index in the direction orthogonal to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction.

[0023] (2) In-Plane Phase Difference (Re) "Re(λ)" is the in-plane phase difference at 23°C measured by light of wavelength λ nm. For example, "Re(550)" is the in-plane phase difference at 23°C measured by light of wavelength 550 nm. When the thickness of the layer (film) is set to d (nm), Re(λ) is calculated by the formula: Re(λ) = (nx-ny) x d.

[0024] (3) Phase Difference in Thickness Direction (Rth) "Rth(λ)" is the phase difference in the thickness direction at 23°C measured by light of wavelength λ nm. For example, "Rth(550)" is the phase difference in the thickness direction at 23°C measured by light of wavelength 550 nm. When the thickness of the layer (film) is set to d (nm), Rth(λ) is calculated by the formula: Rth(λ) = (nx-nz) x d.

[0025] (4) Nz Coefficient The Nz coefficient is calculated by Nz = Rth / Re.

[0026] (5) Angle When an angle is mentioned in the present specification, the angle includes both clockwise and counterclockwise with respect to a reference direction. Thus, for example, "45°" means ±45°.

[0027] (6) Substantially Parallel or Orthogonal The expressions "substantially orthogonal" and "approximately orthogonal" include a case where the angle between two directions is 90°±10°, preferably 90°±7°, and further preferably 90°±5°. The expressions "substantially parallel" and "approximately parallel" include a case where the angle between two directions is 0°±10°, preferably 0°±7°, and further preferably 0°±5°. Furthermore, in the present specification, when abbreviated as "orthogonal" or "parallel", a state that can include substantially orthogonal or substantially parallel is assumed.

[0028] A. Summary of Polarizing Film Figure 1 is a schematic cross-sectional view of an optical layer stack including a polarizing film of one embodiment of the present application.

[0029] The polarizing film 11 includes a polyvinyl alcohol-based resin (hereinafter, sometimes referred to as a PVA-based resin) and an organic dye. The thickness of the polarizing film 11 is 10 μm or less, preferably 8 μm or less, and more preferably 6 μm or less.

[0030] The polarizing film 11 is dyed with an organic dye different from iodine. Therefore, excellent polarization properties (optical properties; monomer transmittance and / or polarization) can be imparted to the polarizing film, suppressing discoloration under humidified conditions (typically relative humidity above 80%). In particular, discoloration is stably suppressed even at the ends of the polarizing film where discoloration is relatively prone to occur under humidified conditions. Therefore, the polarizing film 11 exhibits excellent durability.

[0031] Furthermore, since the thickness of the polarizing film is below the aforementioned upper limit, there is less thickness unevenness and excellent visibility. In addition, thermal shrinkage of the polarizing film can be suppressed, thus improving the dimensional stability of the polarizing film. Moreover, it is preferable that the thickness of the polarizer can also be made thinner. The lower limit of the polarizing film thickness is typically 1 μm.

[0032] The orientation function of the PVA-based resin contained in the polarizing film 11 is, for example, 0.40 or less, preferably 0.38 or less, more preferably 0.35 or less, even more preferably 0.30 or less, and especially preferably 0.28 or less.

[0033] If the orientation function of the PVA-based resin contained in the polarizing film is below the aforementioned upper limit, the thermal shrinkage of the polarizing film can be stably suppressed. The lower limit of the orientation function of the PVA-based resin contained in the polarizing film is representatively 0.20. It should be noted that the orientation function of the PVA-based resin is determined, for example, using a Fourier transform infrared spectrophotometer (FT-IR) with polarized light as the measurement light, by attenuated total reflection (ATR) spectroscopy. Specifically, the measurement is performed with the polarizing film's stretching direction parallel and perpendicular to the polarization direction of the measurement light, and the absorbance spectrum at 2941 cm⁻¹ is used. -1 The strength is calculated according to the following formula. Wherein, strength I is based on a density of 3330 cm³. -1 2941 cm, used as a reference peak -1 / 3330cm -1 The value of f. It should be noted that f=1 indicates perfect orientation, and f=0 indicates random orientation. Furthermore, 2941cm is considered... -1 The peak is due to the absorption of vibrations in the PVA backbone (-CH2-) in the polarization film.

[0034] f = (3) <cos 2 θ>-1) / 2 = (1-D) / [c(2D+1)] =-2×(1-D) / (2D+1) in, In c = (3cos2 β = 90° in the case of β = 1) / 2 and 2941 cm -1 β = 90° in the case of β = 1) / 2 and 2941 cm

[0035] θ: angle of the molecular chain with respect to the stretching direction β: angle of the transition dipole moment with respect to the molecular chain axis D = (I ⊥ ) / (I / / ) (in this case, the more the PVA molecules are oriented, the greater D becomes) I ⊥ : absorption intensity in the case where the polarization direction of the measuring light is perpendicular to the stretching direction of the polarizing film I / / : absorption intensity in the case where the polarization direction of the measuring light is parallel to the stretching direction of the polarizing film Further, if the orientation function of the PVA-based resin included in the polarizing film 11 is equal to or lower than the above upper limit, improvement of the puncture strength of the polarizing film can be sought.

[0036] The puncture strength of the polarizing film 11 is, for example, 25.0 gf / μm or more, preferably 30.0 gf / μm or more, more preferably 35.0 gf / μm or more, further preferably 40.0 gf / μm or more, and particularly preferably 45.0 gf / μm or more. If the puncture strength of the polarizing film is equal to or higher than the above lower limit, the polarizing film can be significantly inhibited from breaking along the absorption axis direction. As a result, a polarizing film (and as a result, a polarizing plate, an optical laminate) having very excellent flexibility can be obtained. The puncture strength indicates the cracking resistance of the polarizing film when the polarizing film is punctured with a prescribed strength. The puncture strength can be expressed, for example, as the strength (breaking strength) at which the polarizing film cracks when a prescribed needle is installed in a compression testing machine and punctured into the polarizing film at a prescribed speed. Note that the puncture strength refers to the puncture strength per unit thickness (1 μm) of the polarizing film. The upper limit of the puncture strength is, for example, 80 gf / μm.

[0037] As the organic dye that can be used in the present application, any appropriate organic dye having dichroism and excellent dyeing properties for a polyvinyl alcohol-based resin can be used. For example, polymethine dyes, cyanine dyes, merocyanine dyes, rhodacyanine dyes, trinuclear merocyanine dyes, allopolar dyes, hemicyanine dyes, styryl dyes, and azo-based dyes can be used, of which azo-based dyes are preferred from the viewpoint of dichroism of the polarizing film and durability against discoloration in a humidified environment.

[0038] As the organic dye of the azo-based dye, for example, azo-based compounds described in "Application of Functional Dyes" (edited by Masahiro Iriyama, CMC Publishing), pages 98-100, C.I. Direct Yellow 12, C.I. Direct Yellow 28, C.I. Direct Yellow 44, C.I. Direct Orange 26, C.I. Direct Orange 39, C.I. Direct Orange 107, C.I. Direct Red 2, C.I. Direct Red 31, C.I. Direct Red 79, C.I. Direct Red 81, C.I. Direct Red 247, C.I. Direct Green 80, C.I. Direct Green 59, and organic dyes described in Japanese Patent Application Publication No. 2001-33627, Japanese Patent Application Publication No. 2002-296417, Japanese Patent Application Publication No. 2003-215338, WO2004 / 092282, Japanese Patent Application Publication No. 2001-056412, Japanese Patent Application Publication No. 2001-027708, Japanese Patent Application Publication No. Hei 11-218611, and Japanese Patent Application Publication No. Hei 11-218610 can be listed. These dichromatic dyes can be listed in addition to free acids, alkali metal salts (for example, Na salt, K salt, and Li salt), ammonium salts, amine salts, or complex salts (for example, Cu complex, Ni complex, and Co complex), and the like. Such azo compounds have inherent color tones such as yellow, red, and blue, and thus are used alone or in combination with two or more kinds in view of the optical characteristics and color tone of the target polarizing film. The organic dye-based polarizing film has high optical characteristics, and can be adjusted to an arbitrary color tone, and thus the display quality can be improved in the image display device used. Note that the display quality here refers to contrast, brightness, chroma, color tone of the displayed image, and further refers to the color tone of the reflected color in the black screen when no image is displayed, and aesthetic appearance.

[0039] In view of the performance of high optical characteristics, the polarizing film using the above-described organic dye can generally be suitably formed using a PVA-based resin as the orientation base material. The organic dye-based polarizing film is generally formed by adsorbing the organic dye on the PVA-based resin in a wet process and stretching the resin.

[0040] In view of the optical characteristics of the polarizing film, and particularly the dyeability and orientation of the PVA-based resin used in the polarizing film, the polarizing film preferably contains at least a first dye, which is an azo compound or a salt thereof having a urea-based skeleton represented by the following formula (1), as the organic dye. The first dye does not impair the inherent dyeability and orientation of the dye even in the PVA-based resin, and thus contributes to the performance of high polarizing characteristics in the entire visible light region. Further, the first dye has high performance of polarizing characteristics, and thus can maintain the desired optical characteristics even if the stretching ratio for dye orientation is moderately reduced.

[0041] Further, in one embodiment, the polarizing film preferably contains, as the organic dye, a second dye which is an azo compound represented by the following formula (2) or a salt thereof, and a third dye which is an azo compound represented by the following formula (3) or a salt thereof, in addition to the first dye. Such a polarizing film containing a plurality of organic dyes can be adjusted to a desired hue, and can have a corresponding polarizing property in an image display device requiring a high display quality.

[0042] In one embodiment, the polarizing film contains at least a first dye which is an azo compound having a urea skeleton represented by the following formula (1) or a salt thereof.

[0043] [Chemical Formula 1] In formula (1), Ay1and Ay2are each independently a naphthyl group which can have a substituent, or a phenyl group which can have a substituent, s and t are each independently 0 or 1, and either one of s or t is 1, and Ry1to Ry8each independently represent a hydrogen atom or a substituent: the above-mentioned phenyl group which can have a substituent refers to a phenyl group having at least one or more substituents selected from the group consisting of a sulfo group, a carboxyl group, an alkyl group having a sulfo group with a carbon number of 1 to 4, an alkyl group with a carbon number of 1 to 4, an alkoxy group with a carbon number of 1 to 4, a halogen atom, a nitro group, an amino group, an alkyl group-substituted amino group with a carbon number of 1 to 4, and an alkyl group-substituted acylamino group with a carbon number of 1 to 4, and the naphthyl group which can have a substituent refers to a naphthyl group which can have a substituent selected from the group consisting of a hydroxyl group, an alkoxy group having a sulfo group with a carbon number of 1 to 4, and a sulfo group: Ry1, Ry2, Ry7, and Ry8are each independently a hydrogen atom, an alkyl group with a carbon number of 1 to 4, or an alkoxy group with a carbon number of 1 to 4, and Ry3to Ry6are each independently a hydrogen atom, an alkyl group with a carbon number of 1 to 4, an alkoxy group with a carbon number of 1 to 4, or an alkoxy group having a sulfo group with a carbon number of 1 to 4.

[0044] If the organic dye contains the above-mentioned first dye, the thermal shrinkage of the polarizing film can be stably suppressed, and the improvement of the polarizing property of the polarizing film can be sought.

[0045] In one embodiment, the polarizing film contains, in addition to the above-mentioned first dye, a second dye which is an azo compound represented by the following formula (2) or a salt thereof, and a third dye which is an azo compound represented by the following formula (3) or a salt thereof.

[0046] [Chemical Formula 2] In formula (2), Ar 11 represents a phenyl group which can have a substituent, or a naphthyl group which can have a substituent, and Rr 11 to Rr 16respectively independently represent a hydrogen atom, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 with a sulfo group, Xr 11 respectively independently represent a hydrogen atom, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 with a sulfo group, Xr 15 respectively independently represent a hydrogen atom, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 with a sulfo group, Xr 16 respectively independently represent a hydrogen atom, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 with a sulfo group, Xr 11 respectively independently represent a hydrogen atom, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 with a sulfo group, Xr 12 respectively independently represent a hydrogen atom, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 with a sulfo group, Xr [Chemical Formula 3] In formula (3), A is the same as Ar of the above formula (2) 11 Also, or is a substituent represented by the following general formula (4), [Chemical Formula 4] (In formula (4), A1 represents a nitro group or an amino group) R1 to R4, R6, and Rr of the above formula (2) 11 Rr 14 Also, X is the same as Xr of the above formula (2) 11 Also, m and n are respectively 0 or 1.

[0047] If the polarizing film contains the above-mentioned first dye, second dye, and third dye, further improvement of the polarizing property of the polarizing film can be sought, and thermal shrinkage of the polarizing film can be more stably suppressed.

[0048] Hereinafter, details of the PVA-based resin and organic dye are described.

[0049] B. Details of the PVA-based resin The PVA-based resin is an alignment base material for forming a polarizing film by adsorbing and orienting a dichroic substance. As the PVA-based resin, for example, polyvinyl alcohol, acetal-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and the like can be exemplified. These PVA-based resins can be used alone, or two or more kinds of PVA-based resins having different modified kinds or modification rates, polymerization degrees, saponification degrees, and the like can be used in combination.

[0050] The PVA-based resin used in the present application, as described later in the following method for producing a polarizing film, can be suitably used as an alignment base material in terms of thinning of the polarizing film, using a PVA-based resin layer formed by applying a coating liquid containing the resin onto a resin base material. At this time, the coating liquid contains various additives to form the PVA-based resin layer, and thus the PVA-based resin layer formed contains the additives. As compared with the case of using a separate film of a PVA-based resin available on the market as a raw material, the PVA-based resin layer formed on the resin base material can extremely pursue thinning of the polarizing film in a manner such that the thickness of the polarizing film is 10 μm or less, preferably 8 μm or less, and more preferably 6 μm or less, and even in the case of a thin film, stable processability can be achieved.

[0051] The PVA-based resin typically contains polyvinyl alcohol. The polyvinyl alcohol can be obtained by saponifying polyvinyl acetate.

[0052] The content ratio of the polyvinyl alcohol in the PVA-based resin is, for example, 80% by mass or more, preferably 88% by mass or more, and for example, 100% by mass or less, and further for example, 95% by mass or less.

[0053] In one embodiment, the PVA-based resin contains, in addition to the polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol.

[0054] The content ratio of the acetoacetyl-modified polyvinyl alcohol in the PVA-based resin is, for example, 5% by mass or more, preferably 8% by mass or more, and for example, 20% by mass or less, and preferably 12% by mass or less. If the content ratio of the acetoacetyl-modified polyvinyl alcohol in the PVA-based resin is within the above range, the polarizing film can be stably dyed with an organic dye, and an increase in the mechanical strength of the polarizing film can be pursued.

[0055] The saponification degree of the PVA-based resin is typically 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, more preferably 99.0 mol% to 99.93 mol%, and further preferably 99.0 mol% to 99.5 mol%. The saponification degree can be measured in accordance with JIS K 6726-1994. By using a PVA-based resin having such a saponification degree, a thin polarizing film having excellent durability can be achieved.

[0056] The average polymerization degree of the PVA-based resin can be appropriately selected depending on the purpose. The average polymerization degree is, for example, 1000 or more, preferably 1500 or more, more preferably 2000 or more, further preferably 3000 or more, and for example, 10000 or less, preferably 6000 or less, further preferably 4300 or less. Note that the average polymerization degree can be measured in accordance with JIS K 6726-1994.

[0057] C. Details of the organic dye C-1. First dye The first dye is an azo compound or a salt thereof having a urea-based skeleton represented by the above formula (1). As such a first dye, for example, the azo compound or the salt thereof described in International Publication No. 2019 / 124161 can be cited. The entire description of this publication is incorporated herein by reference.

[0058] In one aspect, it is preferable that, in the above formula (1), Ay1and Ay2are each independently a phenyl group which can have a substituent selected from the group consisting of a sulfo group having a carbon number of 1 to 4, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a carboxyl group, a halogen group, a nitro group, a sulfo group, a substituted or unsubstituted amino group, and an amido group, s and t are each independently 0 or 1, and either one of s or t is 1, Ry1, Ry2, Ry7, and Ry8are each independently a hydrogen atom, an alkyl group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4, and Ry3to Ry6are each independently a hydrogen atom, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 having a sulfo group. More preferably, Ay1and Ay2are each independently a phenyl group which can have a substituent selected from the group consisting of a carboxyl group, a halogen group, and a sulfo group, s and t are each independently 0 or 1, and either one of s or t is 1, Ry1, Ry2, Ry7, and Ry8are each independently a hydrogen atom, a methyl group, or a methoxy group, and Ry3to Ry6are each independently a hydrogen atom, a methyl group, a methoxy group, or a 3-sulfopropoxy group. Further preferably, Ay1and Ay2are each independently a 4-sulfophenyl group, a 4-carboxyphenyl group, a 4-chloro-4-carboxyphenyl group, or a 2,4-disulfophenyl group, s and t are each independently 0 or 1, and either one of s or t is 1, Ry1, Ry2, Ry7, and Ry8are each independently a hydrogen atom, a methyl group, or a methoxy group, and Ry3to Ry6are each independently a hydrogen atom, a methyl group, a methoxy group, or a 3-sulfopropoxy group. Particularly preferably, Ay1and Ay2are each independently any one of a combination of a 4-sulfophenyl group and a 4-carboxyphenyl group, a combination of a 4-carboxyphenyl group and a 4-chloro-3-carboxyphenyl group, a combination of a 4-sulfophenyl group and a 4-chloro-3-carboxyphenyl group, or a combination of a 4-carboxyphenyl group and a 2,4-disulfophenyl group, s and t are each independently 0 or 1, and either one of s or t is 1, Ry1, Ry2, Ry7, and Ry8are each independently a hydrogen atom, a methyl group, or a methoxy group, and Ry3to Ry6are each independently a hydrogen atom, a methyl group, a methoxy group, or a 3-sulfopropoxy group.

[0059] In one aspect, it is preferable that, in the above formula (1), Ay1and Ay2are each independently naphthyl which can have a substituent selected from the group consisting of alkoxyl group having sulfogroup of carbon number 1 to 4 and sulfogroup, or phenyl which can have alkoxyl group having sulfogroup of carbon number 1 to 4, alkyl group of carbon number 1 to 4, alkoxyl group of carbon number 1 to 4, carboxyl group, halogen group, nitro group, sulfogroup, substituted or unsubstituted amino group, amido group, either of Ay1or Ay2is naphthyl which can have a substituent selected from the group consisting of alkoxyl group having sulfogroup of carbon number 1 to 4 and sulfogroup, s and t are each independently 0 or 1, and either of s or t is 1, Ry1, Ry2, Ry7and Ry8are each independently hydrogen atom, alkyl group of carbon number 1 to 4, or alkoxyl group of carbon number 1 to 4, and Ry3to Ry6are each independently hydrogen atom, alkyl group of carbon number 1 to 4, alkoxyl group of carbon number 1 to 4, or alkoxyl group of carbon number 1 to 4 having sulfogroup. More preferably, Ay1and Ay2are each independently naphthyl which can have a substituent selected from the group consisting of alkoxyl group having sulfogroup of carbon number 1 to 4 and sulfogroup, or phenyl which can have a substituent selected from the group consisting of carboxyl group, halogen group and sulfogroup, either of Ay1or Ay2is naphthyl which can have a substituent selected from the group consisting of alkoxyl group having sulfogroup of carbon number 1 to 4 and sulfogroup, s and t are each independently 0 or 1, and either of s or t is 1, Ry1, Ry2, Ry7and Ry8are each independently hydrogen atom, methyl group, or methoxyl group, and Ry3to Ry6are each independently hydrogen atom, methyl group, methoxyl group, or 3-sulfopropoxyl group. Further preferably, Ay1and Ay2are each independently naphthyl which can have a substituent selected from the group consisting of 3-sulfopropoxyl group and sulfogroup, s and t are each independently 0 or 1, and either of s or t is 1, Ry1, Ry2, Ry7and Ry8are each independently hydrogen atom, methyl group, or methoxyl group, and Ry3to Ry6are each independently hydrogen atom, methyl group, methoxyl group, or 3-sulfopropoxyl group. Particularly preferably, Ay1and Ay2are each 6,8-disulfonaphthyl or 6-sulfo-8-(3-sulfopropoxyl)naphthyl, s and t are each independently 0 or 1, and either of s or t is 1, Ry1, Ry2, Ry7and Ry8are each independently hydrogen atom, methyl group, or methoxyl group, and Ry3to Ry6are each independently hydrogen atom, methyl group, methoxyl group, or 3-sulfopropoxyl group. Most preferably, Ay1and Ay2are each 6,8-disulfonaphthyl or 6-sulfo-8-(3-sulfopropoxyl)naphthyl, s and t are each 1, Ry1, Ry2, Ry7and Ry8are each independently hydrogen atom, methyl group, or methoxyl group, and Ry3to Ry6are each independently hydrogen atom, methyl group, methoxyl group, or 3-sulfopropoxyl group.

[0060] As such the first dye, specifically, the following compounds Examples 1 to 268 can be exemplified.

[0061] (Cpd. Ex. 1) [Formula 1-1] (Cpd. Ex. 2) [Formula 1-2] (Cpd. Ex. 3) [Formula 1-3] (Cpd. Ex. 4) [Formula 1-4] (Cpd. Ex. 5) [Formula 1-5] (Cpd. Ex. 6) [Formula 1-6] (Cpd. Ex. 7) [Formula 1-7] (Cpd. Ex. 8) [Formula 1-8] (Cpd. Ex. 9) [Formula 1-9] (Cpd. Ex. 10) [Formula 1-10] (Cpd. Ex. 11) [Formula 1-11] (Cpd. Ex. 12) [Formula 1-12] (Cpd. Ex. 13) [Formula 1-13] (Cpd. Ex. 14) [Formula 1-14] (Cpd. Ex. 15) [Formula 1-15] (Compound Example 16) [Chemical Formula 1-16] (Compound Example 17) [Chemical Formula 1-17] (Compound Example 18) [Chemical Formula 1-18] (Compound Example 19) [Chemical Formula 1-19] (Compound Example 20) [Chemical Formula 1-20] (Compound Example 21) [Chemical Formula 1-21] (Compound Example 22) [Chemical Formula 1-22] (Compound Example 23) [Chemical Formula 1-23] (Compound Example 24) [Chemical Formula 1-24] (Compound Example 25) [Chemical Formula 1-25] (Compound Example 26) [Chemical Formula 1-26] (Compound Example 27) [Chemical Formula 1-27] (Compound Example 28) [Chemical Formula 1-28] (Compound Example 29) [Chemical Formula 1-29] (Compound Example 30) [Chemical Formula 1-30] (Compound Example 31) [Chemical Formula 1-31] (Compound Example 32) [Chemical Formula 1-32] (Compound Example 33) [Chemical Formula 1-33] (Compound Example 34) [Chemical Formula 1-34] (Compound Example 35) [Chemical Formula 1-35] (Compound Example 36) [Chemical Formula 1-36] (Compound Example 37) [Chemical Formula 1-37] (Compound Example 38) [Chemical Formula 1-38] (Compound Example 39) [Chemical Formula 1-39] (Compound Example 40) [Chemical Formula 1-40] (Compound Example 41) [Chemical Formula 1-41] (Compound Example 42) [Chemical Formula 1-42] (Compound Example 43) [Chemical Formula 1-43] (Compound Example 44) [Chemical Formula 1-44] (Compound Example 45) [Chemical Formula 1-45] (Compound Example 46) [Chemical Formula 1-46] (Compound Example 47) [Chemical Formula 1-47] (Compound Example 48) [Chemical Formula 1-48] (Compound Example 49) [Chemical Formula 1-49] (Compound Example 50) [Chemical Formula 1-50] (Compound Example 51) [Chemical Formula 1-51] (Compound Example 52) [Chemical Formula 1-52] (Compound Example 53) [Chemical Formula 1-53] (Compound Example 54) [Chemical Formula 1-54] (Compound Example 55) [Chemical Formula 1-55] (Compound Example 56) [Chemical Formula 1-56] (Compound Example 57) [Chemical Formula 1-57] (Compound Example 58) [Chemical Formula 1-58] (Compound Example 59) [Chemical Formula 1-59] (Compound Example 60) [Chemical Formula 1-60] (Compound Example 61) [Chemical Formula 1-61] (Compound Example 62) [Chemical Formula 1-62] (Compound Example 63) [Chemical Formula 1-63] (Compound Example 64) [Chemical Formula 1-64] (Compound Example 65) [Chemical Formula 1-65] (Compound Example 66) [Chemical Formula 1-66] (Compound Example 67) [Chemical Formula 1-67] (Compound Example 68) [Chemical Formula 1-68] (Compound Example 69) [Chemical Formula 1-69] (Compound Example 70) [Chemical Formula 1-70] (Compound Example 71) [Chemical Formula 1-71] (Compound Example 72) [Chemical Formula 1-72] (Compound Example 73) [Chemical Formula 1-73] (Compound Example 74) [Chemical Formula 1-74] (Compound Example 75) [Chemical Formula 1-75] (Compound Example 76) [Chemical Formula 1-76] (Compound Example 77) [Chemical Formula 1-77] (Compound Example 78) [Chemical Formula 1-78] (Compound Example 79) [Chemical Formula 1-79] (Compound Example 80) [Chemical Formula 1-80] (Compound Example 81) [Chemical Formula 1-81] (Compound Example 82) [Chemical Formula 1-82] (Compound Example 83) [Chemical Formula 1-83] (Compound Example 84) [Chemical Formula 1-84] (Compound Example 85) [Chemical Formula 1-85] (Compound Example 86) [Chemical Formula 1-86] (Compound Example 87) [Chemical Formula 1-87] (Compound Example 88) [Chemical Formula 1-88] (Compound Example 89) [Chemical Formula 1-89] (Compound Example 90) [Chemical Formula 1-90] (Compound Example 91) [Chemical Formula 1-91] (Compound Example 92) [Chemical Formula 1-92] (Compound Example 93) [Chemical Formula 1-93] (Compound Example 94) [Chemical Formula 1-94] (Compound Example 95) [Chemical Formula 1-95] (Compound Example 96) [Chemical Formula 1-96] (Compound Example 97) [Chemical Formula 1-97] (Compound Example 98) [Chemical Formula 1-98] (Compound Example 99) [Chemical Formula 1-99] (Compound Example 100) [Chemical Formula 1-100] (Compound Example 101) [Chemical Formula 1-101] (Compound Example 102) [Chemical Formula 1-102] (compound example 103) [Chemical Formula 1-103] (compound example 104) [Chemical Formula 1-104] (compound example 105) [Chemical Formula 1-105] (compound example 106) [Chemical Formula 1-106] (compound example 107) [Chemical Formula 1-107] (compound example 108) [Chemical Formula 1-108] (compound example 109) [Chemical Formula 1-109] (compound example 110) [Chemical Formula 1-110] (compound example 111) [Chemical Formula 1-111] (compound example 112) [Chemical Formula 1-112] (compound example 113) [Chemical Formula 1-113] (compound example 114) [Chemical Formula 1-114] (compound example 115) [Chemical Formula 1-115] (compound example 116) [Chemical Formula 1-116] (compound example 117) [Chemical Formula 1-117] (compound example 118) [Chemical Formula 1-118] (compound example 119) [Chemical Formula 1-119] (compound example 120) [Chemical Formula 1-120] (compound example 121) [Chemical Formula 1-121] (compound example 122) [Chemical Formula 1-122] (compound example 123) [Chemical Formula 1-123] (compound example 124) [Chemical Formula 1-124] (compound example 125) [Chemical Formula 1-125] (compound example 126) [Chemical Formula 1-126] (compound example 127) [Chemical Formula 1-127] (compound example 128) [Chemical Formula 1-128] (compound example 129) [Chemical Formula 1-129] (compound example 130) [Chemical Formula 1-130] (compound example 131) [Chemical formula 1-131] (compound example 132) [Chemical formula 1-132] (compound example 133) [Chemical formula 1-133] (compound example 134) [Chemical formula 1-134] (compound example 135) [Chemical formula 1-135] (compound example 136) [Chemical formula 1-136] (compound example 137) [Chemical formula 1-137] (compound example 138) [Chemical formula 1-138] (compound example 139) [Chemical formula 1-139] (compound example 140) [Chemical formula 1-140] (compound example 141) [Chemical formula 1-141] (compound example 142) [Chemical formula 1-142] (compound example 143) [Chemical formula 1-143] (compound example 144) [Chemical formula 1-144] (Compound Example 145) [Chemical Formula 1-145] (Compound Example 146) [Chemical Formula 1-146] (Compound Example 147) [Chemical Formula 1-147] (Compound Example 148) [Chemical Formula 1-148] (Compound Example 149) [Chemical Formula 1-149] (Compound Example 150) [Chemical Formula 1-150] (Compound Example 151) [Chemical Formula 1-151] (Compound Example 152) [Chemical Formula 1-152] (Compound Example 153) [Chemical Formula 1-153] (Compound Example 154) [Chemical Formula 1-154] (Compound Example 155) [Chemical Formula 1-155] (Compound Example 156) [Chemical Formula 1-156] (Compound Example 157) [Chemical Formula 1-157] (Compound Example 158) [Chemical Formula 1-158] (Compound Example 159) [Chemical Formula 1-159] (Compound Example 160) [Chemical Formula 1-160] (Compound Example 161) [Chemical Formula 1-161] (Compound Example 162) [Chemical Formula 1-162] (Compound Example 163) [Chemical Formula 1-163] (Compound Example 164) [Chemical Formula 1-164] (Compound Example 165) [Chemical Formula 1-165] (Compound Example 166) [Chemical Formula 1-166] (Compound Example 167) [Chemical Formula 1-167] (Compound Example 168) [Chemical Formula 1-168] (Compound Example 169) [Chemical Formula 1-169] (Compound Example 170) [Chemical Formula 1-170] (Compound Example 171) [Chemical Formula 1-171] (Compound Example 172) [Chemical Formula 1-172] (compound example 173) [Chemical Formula 1-173] (compound example 174) [Chemical Formula 1-174] (compound example 175) [Chemical Formula 1-175] (compound example 176) [Chemical Formula 1-176] (compound example 177) [Chemical Formula 1-177] (compound example 178) [Chemical Formula 1-178] (compound example 179) [Chemical Formula 1-179] (compound example 180) [Chemical Formula 1-180] (compound example 181) [Chemical Formula 1-181] (compound example 182) [Chemical Formula 1-182] (compound example 183) [Chemical Formula 1-183] (compound example 184) [Chemical Formula 1-184] (compound example 185) [Chemical Formula 1-185] (compound example 186) [Chemical Formula 1-186] (Compound Example 187) [Chemical Formula 1-187] (Compound Example 188) [Chemical Formula 1-188] (Compound Example 189) [Chemical Formula 1-189] (Compound Example 190) [Chemical Formula 1-190] (Compound Example 191) [Chemical Formula 1-191] (Compound Example 192) [Chemical Formula 1-192] (Compound Example 193) [Chemical Formula 1-193] (Compound Example 194) [Chemical Formula 1-194] (Compound Example 195) [Chemical Formula 1-195] (Compound Example 196) [Chemical Formula 1-196] (Compound Example 197) [Chemical Formula 1-197] (Compound Example 198) [Chemical Formula 1-198] (Compound Example 199) [Chemical Formula 1-199] (Compound Example 200) [Chemical Formula 1-200] (compound example 201) [Chemical formula 1-201] (compound example 202) [Chemical formula 1-202] (compound example 203) [Chemical formula 1-203] (compound example 204) [Chemical formula 1-204] (compound example 205) [Chemical formula 1-205] (compound example 206) [Chemical formula 1-206] (compound example 207) [Chemical formula 1-207] (compound example 208) [Chemical formula 1-208] (compound example 209) [Chemical formula 1-209] (compound example 210) [Chemical formula 1-210] (compound example 211) [Chemical formula 1-211] (compound example 212) [Chemical formula 1-212] (compound example 213) [Chemical formula 1-213] (compound example 214) [Chemical formula 1-214] (Compound Example 215) [Chemical Formula 1-215] (Compound Example 216) [Chemical Formula 1-216] (Compound Example 217) [Chemical Formula 1-217] (Compound Example 218) [Chemical Formula 1-218] (Compound Example 219) [Chemical Formula 1-219] (Compound Example 220) [Chemical Formula 1-220] (Compound Example 221) [Chemical Formula 1-221] (Compound Example 222) [Chemical Formula 1-222] (Compound Example 223) [Chemical Formula 1-223] (Compound Example 224) [Chemical Formula 1-224] (Compound Example 225) [Chemical Formula 1-225] (Compound Example 226) [Chemical Formula 1-226] (Compound Example 227) [Chemical Formula 1-227] (Compound Example 228) [Chemical Formula 1-228] (compound example 229) [Chemical Formula 1-229] (compound example 230) [Chemical Formula 1-230] (compound example 231) [Chemical Formula 1-231] (compound example 232) [Chemical Formula 1-232] (compound example 233) [Chemical Formula 1-233] (compound example 234) [Chemical Formula 1-234] (compound example 235) [Chemical Formula 1-235] (compound example 236) [Chemical Formula 1-236] (compound example 237) [Chemical Formula 1-237] (compound example 238) [Chemical Formula 1-238] (compound example 239) [Chemical Formula 1-239] (compound example 240) [Chemical Formula 1-240] (compound example 241) [Chemical Formula 1-241] (compound example 242) [Chemical Formula 1-242] (compound example 243) [Chemical Formula 1-243] (compound example 244) [Chemical Formula 1-244] (compound example 245) [Chemical Formula 1-245] (compound example 246) [Chemical Formula 1-246] (compound example 247) [Chemical Formula 1-247] (compound example 248) [Chemical Formula 1-248] (compound example 249) [Chemical Formula 1-249] (compound example 250) [Chemical Formula 1-250] (compound example 251) [Chemical Formula 1-251] (compound example 252) [Chemical Formula 1-252] (compound example 253) [Chemical Formula 1-253] (compound example 254) [Chemical Formula 1-254] (compound example 255) [Chemical Formula 1-255] (compound example 256) [Chemical Formula 1-256] (Compound Example 257) [Chemical Formula 1-257] (Compound Example 258) [Chemical Formula 1-258] (Compound Example 259) [Chemical Formula 1-259] (Compound Example 260) [Chemical Formula 1-260] (Compound Example 261) [Chemical Formula 1-261] (Compound Example 262) [Chemical Formula 1-262] (Compound Example 263) [Chemical Formula 1-263] (Compound Example 264) [Chemical Formula 1-264] (Compound Example 265) [Chemical Formula 1-265] (Compound Example 266) [Chemical Formula 1-266] (Compound Example 267) [Chemical Formula 1-267] (Compound Example 268) [Chemical Formula 1-268] These first dyes can be used alone or in combination.

[0062] Among the first dyes, compounds represented by the aforementioned Compound Example 25, the aforementioned Compound Example 140, the aforementioned Compound Example 167, the aforementioned Compound Example 177, the aforementioned Compound Example 180, and the aforementioned Compound Example 241 can be preferably exemplified.

[0063] C-2. Second dye The second dye is typically an azo compound represented by the aforementioned formula (2) or a salt thereof.

[0064] In the aforementioned general formula (2), Ar 11 represents a phenyl group having a substituent, or a naphthyl group having a substituent, Rr 11 ~Rr 16 independently represent a hydrogen atom, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 and having a sulfo group, Xr11represents an amino group which can have a substituent selected from the group consisting of an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, a benzoyl group which can have a substituent selected from the group consisting of an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, a phenylamino group which can have a substituent selected from the group consisting of an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, a benzoyl amino group which can have a substituent selected from the group consisting of an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, a phenylazo group which can have any of an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a sulfo group, a hydroxyl group, an amino group, or a substituted amino group, or a naphthotriazolyl group which can have a substituent selected from the group consisting of an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, m1and n1independently represent 0 or 1, and in the case where m1and n1are 1, Rr 15 and Rr 16 independently represent a hydrogen atom, an alkyl group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 and having a sulfo group. Ar 11 represents a phenyl group having a substituent, or a naphthyl group having a substituent, but in the case where Ar 11In the case of the phenyl group having a substituent, the phenyl group preferably has at least one sulfogroup or carboxyl group as the substituent, and in the case of the phenyl group having two or more substituents, at least one of the substituents is a sulfogroup or a carboxyl group, and the other substituents are preferably a sulfogroup, a carboxyl group, an alkyl group having 1 to 4 carbons, an alkoxy group having 1 to 4 carbons, an alkoxy group having 1 to 4 carbons having a sulfogroup, a hydroxyl group, a nitro group, an amino group, or a substituted amino group (particularly acetylamino group or an alkylamino group having 1 to 4 carbons), and the other substituents are more preferably a sulfogroup, a carboxyl group, a methyl group, an ethyl group, a methoxy group, an ethoxy group, a hydroxyl group, a nitro group, or an amino group, and particularly preferably a sulfogroup, a carboxyl group, a methyl group, a methoxy group, or an ethoxy group. Furthermore, as the alkoxy group having 1 to 4 carbons having a sulfogroup, a straight-chain alkoxy group is preferable, and the position of the sulfogroup is preferably the end of the alkoxy group. As the alkoxy group having 1 to 4 carbons having a sulfogroup, a 3-sulfopropoxy group or a 4-sulfobutoxy group is more preferable, and a 3-sulfopropoxy group is particularly preferable. The number of substituents on the phenyl group is preferably one or two, and the position of the substituents on the phenyl group is not particularly limited, but is preferably only the 4-position, or a combination of the 2-position and the 4-position, or a combination of the 3-position and the 5-position. In Ar 11 In the case of the phenyl group having a substituent, the phenyl group preferably has at least one sulfogroup or carboxyl group as the substituent, and in the case of the phenyl group having two or more substituents, at least one of the substituents is a sulfogroup or a carboxyl group, and the other substituents are preferably a sulfogroup, a carboxyl group, an alkyl group having 1 to 4 carbons, an alkoxy group having 1 to 4 carbons, an alkoxy group having 1 to 4 carbons having a sulfogroup, a hydroxyl group, a nitro group, an amino group, or a substituted amino group (particularly acetylamino group or an alkylamino group having 1 to 4 carbons), and the other substituents are more preferably a sulfogroup, a carboxyl group, a methyl group, an ethyl group, a methoxy group, an ethoxy group, a hydroxyl group, a nitro group, or an amino group, and particularly preferably a sulfogroup, a carboxyl group, a methyl group, a methoxy group, or an ethoxy group. Furthermore, as the alkoxy group having 1 to 4 carbons having a sulfogroup, a straight-chain alkoxy group is preferable, and the position of the sulfogroup is preferably the end of the alkoxy group. As the alkoxy group having 1 to 4 carbons having a sulfogroup, a 3-sulfopropoxy group or a 4-sulfobutoxy group is more preferable, and a 3-sulfopropoxy group is particularly preferable. The number of substituents on the phenyl group is preferably one or two, and the position of the substituents on the phenyl group is not particularly limited, but is preferably only the 4-position, or a combination of the 2-position and the 4-position, or a combination of the 3-position and the 5-position. In Ar 11 represents an amino group which can have a substituent selected from the group consisting of an alkyl group having 1 to 4 carbons, an alkoxy group having 1 to 4 carbons, a sulfogroup, an amino group, and a substituted amino group, a benzoyl group which can have a substituent selected from the group consisting of an alkyl group having 1 to 4 carbons, an alkoxy group having 1 to 4 carbons, a sulfogroup, an amino group, and a substituted amino group, a phenylamino group which can have a substituent selected from the group consisting of an alkoxy group having 1 to 4 carbons, a sulfogroup, an amino group, and a substituted amino group, a benzoylamino group which can have a substituent selected from the group consisting of an alkoxy group having 1 to 4 carbons, a sulfogroup, an amino group, and a substituted amino group, a phenylazo group which can have a substituent selected from the group consisting of an alkyl group having 1 to 4 carbons, an alkoxy group having 1 to 4 carbons, a sulfogroup, a hydroxyl group, an amino group, and a substituted amino group, or a naphthotriazole group which can have a substituent selected from the group consisting of an alkyl group having 1 to 4 carbons, an alkoxy group having 1 to 4 carbons, a sulfogroup, an amino group, and a substituted amino group.Xr 11Preferably, Xr is amino group which can have one or two substituents selected from the group consisting of methyl group, methoxy group, sulfo group, amino group and alkylamino group having carbon number of 1 to 4, phenylamino group which can have one or two substituents selected from the group consisting of methyl group, methoxy group, sulfo group, amino group and alkylamino group having carbon number of 1 to 4, benzoyl group which can have one substituent selected from the group consisting of amino group and carboxyethylamino group, benzoylamino group which can have one substituent selected from the group consisting of amino group and carboxyethylamino group, or phenylazo group which can have one to three substituents selected from the group consisting of hydroxy group, alkyl group having carbon number of 1 to 4, alkoxy group having carbon number of 1 to 4, amino group and carboxyethylamino group.Xr 11 Preferably, Xr is amino group which can have one or two substituents selected from the group consisting of methyl group, methoxy group, sulfo group, amino group and alkylamino group having carbon number of 1 to 4, phenylamino group which can have one or two substituents selected from the group consisting of methyl group, methoxy group, sulfo group, amino group and alkylamino group having carbon number of 1 to 4, benzoyl group which can have one substituent selected from the group consisting of amino group and carboxyethylamino group, benzoylamino group which can have one substituent selected from the group consisting of amino group and carboxyethylamino group, or phenylazo group which can have one to three substituents selected from the group consisting of hydroxy group, alkyl group having carbon number of 1 to 4, alkoxy group having carbon number of 1 to 4, amino group and carboxyethylamino group.Xr 11 Preferably, Xr is amino group which can have one or two substituents selected from the group consisting of methyl group, methoxy group, sulfo group, amino group and alkylamino group having carbon number of 1 to 4, phenylamino group which can have one or two substituents selected from the group consisting of methyl group, methoxy group, sulfo group, amino group and alkylamino group having carbon number of 1 to 4, benzoyl group which can have one substituent selected from the group consisting of amino group and carboxyethylamino group, benzoylamino group which can have one substituent selected from the group consisting of amino group and carboxyethylamino group, or phenylazo group which can have one to three substituents selected from the group consisting of hydroxy group, alkyl group having carbon number of 1 to 4, alkoxy group having carbon number of 1 to 4, amino group and carboxyethylamino group.Xr 11 ~ Rr 16respectively, independently represent a hydrogen atom, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 having a sulfo group, but are preferably a hydrogen atom, an alkyl group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4, and are more preferably a hydrogen atom, a methyl group, or a methoxy group. As the alkoxy group having a carbon number of 1 to 4 having a sulfo group, a straight-chain alkoxy group is preferable, and the substitution position of the sulfo group is preferably the alkoxy group end. As the alkoxy group having a carbon number of 1 to 4 having a sulfo group, a 3-sulfopropoxy group or a 4-sulfobutoxy group is more preferable, and a 3-sulfopropoxy group is particularly preferable. m1 and n1 are each independently 0 or 1, but in order to obtain good polarizing properties in the polarizing film (polarizing element) of the present embodiment, when either of m1 and n1 is 0, the other is preferably 1. Note that, when m1 and n1 are 1, in order for the polarizing film (polarizing element) of the present embodiment to exhibit the desired properties, Rr 15 and Rr 16 must each independently be a hydrogen atom, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 having a sulfo group, and are preferably a hydrogen atom or a methyl group. As the alkyl group having a carbon number of 1 to 4, the alkoxy group having a carbon number of 1 to 4, and the alkoxy group having a carbon number of 1 to 4 having a sulfo group, an alkyl group having a carbon number of 1 to 3, an alkoxy group having a carbon number of 1 to 3, and an alkoxy group having a carbon number of 3 or 4 having a sulfo group are preferable. Furthermore, the substituted amino group is not particularly limited, but for example, an amino group substituted with an alkyl group having a carbon number of 1 to 4, an amino group substituted with an acyl group, and the like can be exemplified. As the synthesis method of the azo compound represented by General Formula (2) in the form of a free acid, for example, the methods described in Japanese Patent Application Laid-Open No. 9-302250, Japanese Patent No. 2622748, Japanese Patent No. 4662853, International Publication No. 2012 / 108169, International Publication No. 2012 / 108173, and the like can be exemplified, but are not limited thereto. As the azo compound represented by General Formula (2) in the form of a free acid, for example, C.I. Direct Red 117, C.I. Direct Red 127, the azo compounds described in Japanese Patent No. 2622748, the azo compounds described in Japanese Patent No. 4662853, the azo compounds described in International Publication No. 2012 / 108169, and the like can be exemplified. Next, specific examples of the azo compound represented by General Formula (2) in the form of a free acid are exemplified below. Note that, in the following compound examples, the sulfo group and the hydroxyl group are represented in the form of a free acid, but the sulfo group and the hydroxyl group can also be in the form of a salt.

[0065] (Compound Example 269) [Chemical Formula 2-1] (Compound Example 270) [Chemical Formula 2-2] (Cpd.Example 271) [Chem.2-3] (Cpd.Example 272) [Chem.2-4] (Cpd.Example 273) [Chem.2-5] (Cpd.Example 274) [Chem.2-6] (Cpd.Example 275) [Chem.2-7] (Cpd.Example 276) [Chem.2-8] (Cpd.Example 277) [Chem.2-9] (Cpd.Example 278) [Chem.2-10] (Cpd.Example 279) [Chem.2-11] (Cpd.Example 280) [Chem.2-12] (Cpd.Example 281) [Chem.2-13] (Cpd.Example 282) [Chem.2-14] (Cpd.Example 283) [Chem.2-15] (Cpd.Example 284) [Chem.2-16] (Compound Example 285) [Chemical Formula 2-17] (Compound Example 286) [Chemical Formula 2-18] (Compound Example 287) [Chemical Formula 2-19] (Compound Example 288) [Chemical Formula 2-20] (Compound Example 289) [Chemical Formula 2-21] (Compound Example 290) [Chemical Formula 2-22] (Compound Example 291) [Chemical Formula 2-23] (Compound Example 292) [Chemical Formula 2-24] (Compound Example 293) [Chemical Formula 2-25] (Compound Example 294) [Chemical Formula 2-26] (Compound Example 295) [Chemical Formula 2-27] (Compound Example 296) [Chemical Formula 2-28] (Compound Example 297) [Chemical Formula 2-29] (Compound Example 298) [Chemical Formula 2-30] (Compound Example 299) [Chemical Formula 2-31] (Compound Example 300) [Chemical Formula 2-32] (Compound Example 301) [Chemical Formula 2-33] (Compound Example 302) [Chemical Formula 2-34] (Compound Example 303) [Chemical Formula 2-35] (Compound Example 304) [Chemical Formula 2-36] (Compound Example 305) [Chemical Formula 2-37] (Compound Example 306) [Chemical Formula 2-38] (Compound Example 307) [Chemical Formula 2-39] (Compound Example 308) [Chemical Formula 2-40] (Compound Example 309) [Chemical Formula 2-41] (Compound Example 310) [Chemical Formula 2-42] (Compound Example 311) [Chemical Formula 2-43] (Compound Example 312) [Chemical Formula 2-44] (Compound Example 313) [Chemical Formula 2-45] (Compound Example 314) [Chemical Formula 2-46] (Compound Example 315) [Chemical Formula 2-47] (Compound Example 316) [Chemical Formula 2-48] (Compound Example 317) [Chemical Formula 2-49] (Compound Example 318) [Chemical Formula 2-50] (Compound Example 319) [Chemical Formula 2-51] (Compound Example 320) [Chemical Formula 2-52] (Compound Example 321) [Chemical Formula 2-53] (Compound Example 322) [Chemical Formula 2-54] (Compound Example 323) [Chemical Formula 2-55] (Compound Example 324) [Chemical Formula 2-56] (Compound Example 325) [Chemical Formula 2-57] (Compound Example 326) [Chemical Formula 2-58] (Compound Example 327) [Chemical Formula 2-59] (Cpd. Ex. 328) [Chem. 2-60] (Cpd. Ex. 329) [Chem. 2-61] (Cpd. Ex. 330) [Chem. 2-62] (Cpd. Ex. 331) [Chem. 2-63] (Cpd. Ex. 332) [Chem. 2-64] (Cpd. Ex. 333) [Chem. 2-65] (Cpd. Ex. 334) [Chem. 2-66] (Cpd. Ex. 335) [Chem. 2-67] (Cpd. Ex. 336) [Chem. 2-68] (Cpd. Ex. 337) [Chem. 2-69] (Cpd. Ex. 338) [Chem. 2-70] (Cpd. Ex. 339) [Chem. 2-71] (Cpd. Ex. 340) [Chem. 2-72] (Cpd. Ex. 341) [Chem. 2-73] (Cpd. Ex. 342) [Chemical Formula 2-74] (Compound Example 343) [Chemical Formula 2-75] (Compound Example 344) [Chemical Formula 2-76] (Compound Example 345) [Chemical Formula 2-77] (Compound Example 346) [Chemical Formula 2-78] (Compound Example 347) [Chemical Formula 2-79] (Compound Example 348) [Chemical Formula 2-80] (Compound Example 349) [Chemical Formula 2-81] (Compound Example 350) [Chemical Formula 2-82] (Compound Example 351) [Chemical Formula 2-83] (Compound Example 352) [Chemical Formula 2-84] (Compound Example 353) [Chemical Formula 2-85] (Compound Example 354) [Chemical Formula 2-86] (Compound Example 355) [Chemical Formula 2-87] (Compound Example 356) [Chemical Formula 2-88] (Compound Example 357) [Chemical Formula 2-89] (Compound Example 358) [Chemical Formula 2-90] (Compound Example 359) [Chemical Formula 2-91] (Compound Example 360) [Chemical Formula 2-92] (Compound Example 361) [Chemical Formula 2-93] (Compound Example 362) [Chemical Formula 2-94] (Compound Example 363) [Chemical Formula 2-95] (Compound Example 364) [Chemical Formula 2-96] (Compound Example 365) [Chemical Formula 2-97] (Compound Example 366) [Chemical Formula 2-98] (Compound Example 367) [Chemical Formula 2-99] (Compound Example 368) [Chemical Formula 2-100] (Compound Example 369) [Chemical Formula 2-101] (Compound Example 370) [Chemical Formula 2-102] (Cpd. Ex. 371) [Chem. 2-103] (Cpd. Ex. 372) [Chem. 2-104] (Cpd. Ex. 373) [Chem. 2-105] (Cpd. Ex. 374) [Chem. 2-106] (Cpd. Ex. 375) [Chem. 2-107] (Cpd. Ex. 376) [Chem. 2-108] (Cpd. Ex. 377) [Chem. 2-109] (Cpd. Ex. 378) [Chem. 2-110] (Cpd. Ex. 379) [Chem. 2-111] (Cpd. Ex. 380) [Chem. 2-112] (Cpd. Ex. 381) [Chem. 2-113] (Cpd. Ex. 382) [Chem. 2-114] (Cpd. Ex. 383) [Chem. 2-115] (Cpd. Ex. 384) [Chem. 2-116] (Cpd. Ex. 385) [Chem. 2-117] (Cpd. Ex. 386) [Chem. 2-118] (Cpd. Ex. 387) [Chem. 2-119] (Cpd. Ex. 388) [Chem. 2-120] (Cpd. Ex. 389) [Chem. 2-121] (Cpd. Ex. 390) [Chem. 2-122] (Cpd. Ex. 391) [Chem. 2-123] (Cpd. Ex. 392) [Chem. 2-124] (Cpd. Ex. 393) [Chem. 2-125] (Cpd. Ex. 394) [Chem. 2-126] (Cpd. Ex. 395) [Chem. 2-127] (Cpd. Ex. 396) [Chem. 2-128] (Cpd. Ex. 397) [Chem. 2-129] (Cpd. Ex. 398) [Chem. 2-130] (Cpd.Example 399) [Chemical Formula 2-131] (Cpd.Example 400) [Chemical Formula 2-132] (Cpd.Example 401) [Chemical Formula 2-133] (Cpd.Example 402) [Chemical Formula 2-134] (Cpd.Example 403) [Chemical Formula 2-135] (Cpd.Example 404) [Chemical Formula 2-136] (Cpd.Example 405) [Chemical Formula 2-137] (Cpd.Example 406) [Chemical Formula 2-138] (Cpd.Example 407) [Chemical Formula 2-139] (Cpd.Example 408) [Chemical Formula 2-140] (Cpd.Example 409) [Chemical Formula 2-141] (Cpd.Example 410) [Chemical Formula 2-142] (Cpd.Example 411) [Chemical Formula 2-143] (Cpd.Example 412) [Chemical Formula 2-144] (Compound Example 413) [Chemical Formula 2-145] (Compound Example 414) [Chemical Formula 2-146] (Compound Example 415) [Chemical Formula 2-147] (Compound Example 416) [Chemical Formula 2-148] (Compound Example 417) [Chemical Formula 2-149] (Compound Example 418) [Chemical Formula 2-150] (Compound Example 419) [Chemical Formula 2-151] (Compound Example 420) [Chemical Formula 2-152] (Compound Example 421) [Chemical Formula 2-153] (Compound Example 422) [Chemical Formula 2-154] (Compound Example 423) [Chemical Formula 2-155] (Compound Example 424) [Chemical Formula 2-156] (Compound Example 425) [Chemical Formula 2-157] (Compound Example 426) [Chemical Formula 2-158] (Cpd. Example 427) [Chem. 2-159] (Cpd. Example 428) [Chem. 2-160] (Cpd. Example 429) [Chem. 2-161] (Cpd. Example 430) [Chem. 2-162] (Cpd. Example 431) [Chem. 2-163] (Cpd. Example 432) [Chem. 2-164] (Cpd. Example 433) [Chem. 2-165] (Cpd. Example 434) [Chem. 2-166] (Cpd. Example 435) [Chem. 2-167] (Cpd. Example 436) [Chem. 2-168] (Cpd. Example 437) [Chem. 2-169] These 2nd dyes can be used alone or in combination.

[0066] Among the 2nd dyes, the above-mentioned Cpd. Example 269, the above-mentioned Cpd. Example 270, the above-mentioned Cpd. Example 303, the above-mentioned Cpd. Example 311, the above-mentioned Cpd. Example 384 and the above-mentioned Cpd. Example 396 can be preferably exemplified.

[0067] C-3. 3rd dyes The 3rd dye is represented by the above formula (3) or a salt thereof. In formula (3), A is the same as Ar of the above formula (2) 11 Also, or the above formula (4), R1to R4, R6are the same as Rr 11 to Rr 14 of the above formula (2). Also, X is the same as Xr 11 Also, m and n are each 0 or 1. Specific examples of the 3rd dye are shown below.

[0068] (Compound Example 438) [Chemical Formula 3-1] (Compound Example 439) [Chemical Formula 3-2] (Compound Example 440) [Chemical Formula 3-3] (Compound Example 441) [Chemical Formula 3-4] (Compound Example 442) [Chemical Formula 3-5] (Compound Example 443) [Chemical Formula 3-6] (Compound Example 444) [Chemical Formula 3-7] (Compound Example 445) [Chemical Formula 3-8] (Compound Example 446) [Chemical Formula 3-9] (Compound Example 447) [Chemical Formula 3-10] (Compound Example 448) [Chemical Formula 3-11] (Compound Example 449) [Chemical Formula 3-12] (compound example 450) [Chemical formula 3-13] (compound example 451) [Chemical formula 3-14] (compound example 452) [Chemical formula 3-15] (compound example 453) [Chemical formula 3-16] (compound example 454) [Chemical formula 3-17] (compound example 455) [Chemical formula 3-18] (compound example 456) [Chemical formula 3-19] (compound example 457) [Chemical formula 3-20] (compound example 458) [Chemical formula 3-21] (compound example 459) [Chemical formula 3-22] (compound example 460) [Chemical formula 3-23] (compound example 461) [Chemical formula 3-24] (compound example 462) [Chemical formula 3-25] (compound example 463) [Chemical formula 3-26] (Compound Example 464) [Chemical Formula 3-27] (Compound Example 465) [Chemical Formula 3-28] (Compound Example 466) [Chemical Formula 3-29] (Compound Example 467) [Chemical Formula 3-30] (Compound Example 468) [Chemical Formula 3-31] (Compound Example 469) [Chemical Formula 3-32] (Compound Example 470) [Chemical Formula 3-33] These third dyes can be used alone or in combination.

[0069] Among the third dyes, examples of the above-mentioned compounds 454, 455, 441 and 465 are preferably included.

[0070] It should be noted that the azo compounds shown in the above-described examples of compounds of dyes 1 to 3 can be in the form of free acids or salts. Examples of such salts include alkali metal salts such as lithium salts, sodium salts, and potassium salts, as well as organic salts such as ammonium salts and amine salts, with sodium salts being preferred.

[0071] In one embodiment, the polarizing film 11 comprises one first dye, two or more second dyes (preferably two second dyes), and one third dye. Such a polarizing film containing multiple dyes can adjust the hue, for example, through hue values ​​(based on CIE 1976). The color space is calculated based on the single-cell transmittance Ts of a polarizing film 11. and These values ​​are respectively -3 to 3 and the parallel transmittance Tp obtained from the two polarizing films 11. and The adjustment is performed in a manner so that the range of -5 to 5 is respectively attained, and the neutral gray can be set, and the image visibility (particularly, the brilliance of color) in the case of the image display device can be improved.

[0072] D. Characteristics of Polarizing Film The single transmittance Ts of the polarizing film 11 with respect to light having a wavelength of 380 nm to 780 nm is, for example, 38.0% or more, preferably 40.0% or more, and more preferably 40.5% or more. The degree of polarization P of the polarizing film 11 is, for example, 97.5% or more, preferably 98.0% or more, more preferably 98.5% or more, and further preferably 99.0% or more. The polarizing film described above can stably maintain the single transmittance and / or the degree of polarization within the above-described range even when exposed to a humidified environment, because the discoloration in a humidified environment can be suppressed.

[0073] E. Method for Manufacturing Polarizing Film Next, a method for manufacturing the polarizing film of one embodiment will be described.

[0074] The method for manufacturing the polarizing film of one embodiment successively includes a laminate production step, a dry stretching step, a dyeing step, a wet stretching step, and a drying shrinkage step. The method for manufacturing the polarizing film described above can also include a swelling step and / or a cross-linking step. The swelling step is typically performed after the dry stretching step and before the dyeing step. The cross-linking step is typically performed after the dyeing step and before the wet stretching step. The method for manufacturing the polarizing film described above can further include a washing step. The washing step is typically performed after the wet stretching step and before the drying shrinkage step.

[0075] E-1. Laminate Production Step In the laminate production step, the coating solution described above including the PVA-based resin is applied to a long resin substrate by any appropriate method.

[0076] The coating solution is typically a solution obtained by dissolving the PVA-based resin described above in a solvent.

[0077] As the solvent, for example, water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, ethylenediamine, and amine such as diethylenetriamine can be given. These can be used alone or in combination. Of the solvents, water is preferable.

[0078] The PVA-based resin in the coating solution is contained at a proportion of, for example, 3 parts by mass to 20 parts by mass with respect to 100 parts by mass of the solvent. If the resin concentration is such, a uniform coating film that is firmly attached to the resin substrate can be formed.

[0079] In the coating liquid, the above halide can be compounded in the above ratio. Furthermore, an additive can be compounded in the coating liquid. As the additive, for example, a plasticizer, a surfactant can be exemplified. As the plasticizer, for example, a polyhydric alcohol such as ethylene glycol, glycerol can be exemplified. As the surfactant, for example, a nonionic surfactant can be exemplified.

[0080] The resin substrate can be composed of any suitable material. As the material constituting the resin substrate, an amorphous (un-crystallized) polyethylene terephthalate resin can be exemplified, and preferably, an amorphous (not easily crystallized) polyethylene terephthalate resin can be exemplified. As specific examples of the amorphous polyethylene terephthalate resin, a copolymer further containing isophthalic acid as a dicarboxylic acid, a copolymer further containing cyclohexane dimethanol as a diol can be exemplified. Among the resin substrates, an amorphous isophthalic acid copolymerized polyethylene terephthalate film resin substrate can be exemplified.

[0081] The glass transition temperature (Tg) of the resin substrate is, for example, 170°C or lower, and preferably, 120°C or lower. If the Tg of the resin substrate is the above upper limit or lower, excessive crystallization of the PVA-based resin layer can be suppressed, and the stretchability of the laminate can be sufficiently ensured. In addition, the glass transition temperature (Tg) of the resin substrate is, typically, 60°C or higher. Thereby, when the coating liquid is applied to the resin substrate and dried, adverse conditions such as deformation (e.g., generation of unevenness or sagging, wrinkles) of the resin substrate can be suppressed. Note that the glass transition temperature (Tg) is measured in accordance with JIS K 7121.

[0082] The thickness of the resin substrate before stretching is, for example, 20 μm or more, and preferably, 50 μm or more, and is, for example, 300 μm or less, and preferably, 200 μm or less.

[0083] The surface of the resin substrate can be subjected to any suitable surface treatment (e.g., corona treatment), and an easy-adhesion layer can be formed. Thereby, the adhesion of the resin substrate to the PVA-based resin layer can be improved. The surface of the resin substrate is preferably subjected to corona treatment.

[0084] The coating film (coating liquid) formed on the resin substrate is dried at any suitable drying temperature as needed. The drying temperature is, for example, 50°C or higher and 100°C or lower.

[0085] Thereby, a laminate having a PVA-based resin layer and a resin substrate can be produced.

[0086] The thickness of the PVA-based resin layer before dry stretching is, for example, 3 μm or more, and preferably, 5 μm or more, and is, for example, 40 μm or less, and preferably, 30 μm or less.

[0087] E-2. Dry stretching step In the dry stretching process, the laminate having the PVA-based resin layer and the resin base material is stretched in the longitudinal direction in the air. The dry stretching process is otherwise referred to as an air stretching process.

[0088] The stretching method in the dry stretching process can be a fixed-end stretching (for example, a method of stretching using a tenter stretching machine) or a free-end stretching (for example, a method of uniaxially stretching by passing the laminate between rollers having different circumferential speeds).

[0089] The stretching temperature in the dry stretching process is typically 95°C or higher, preferably 120°C or higher, for example, the glass transition temperature (Tg) of the PVA-based resin or higher. The stretching temperature in the dry stretching process is typically 150°C or lower.

[0090] The stretching ratio of the laminate in the dry stretching process is, for example, 2.1 or higher, preferably 2.3 or higher, for example, 4.0 or lower, preferably 3.0 or lower. If the stretching ratio of the laminate is in this range, the orientation of the PVA-based resin layer included in the laminate can be appropriately adjusted.

[0091] The crystallization index in the PVA-based resin layer after the dry stretching process and before the dyeing process is, for example, 0.50 or lower, preferably 0.48 or lower, more preferably 0.40 or lower, further preferably 0.38 or lower. The lower limit of the crystallization index in the PVA-based resin layer is typically 0.20.

[0092] The orientation function in the PVA-based resin layer after the dry stretching process and before the dyeing process is typically less than the orientation function in the polarizing film described above. The orientation function in the PVA-based resin layer after the dry stretching process and before the dyeing process is, for example, 0.35 or lower, preferably 0.28 or lower, more preferably 0.24 or lower, for example, 0.15 or higher.

[0093] If the crystallization index and / or the orientation function in the PVA-based resin layer after the dry stretching process and before the dyeing process is the upper limit described above or lower, the PVA-based resin layer can be smoothly dyed with an organic dye in the dyeing process.

[0094] E-3. Swelling Process In the swelling process, the laminate is typically immersed in a swelling liquid (swelling bath). The swelling liquid is typically water.

[0095] The temperature of the swelling bath is, for example, 10°C or higher, preferably 20°C or higher, for example, 60°C or lower, preferably 50°C or lower. The immersion time in the swelling process is, for example, 10 seconds or longer, preferably 20 seconds or longer, for example, 200 seconds or shorter, preferably 60 seconds or shorter.

[0096] Note that, instead of the swelling step, a non-dissolving step can be performed. In the non-dissolving step, the laminate is typically immersed in a non-dissolving solution (non-dissolving bath). The non-dissolving solution is typically a boric acid aqueous solution. The content ratio of boric acid in the non-dissolving solution is, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of water. The temperature range of the non-dissolving bath is, for example, the same as the temperature range of the swelling bath described above. The immersion time in the non-dissolving step is, for example, the same as the immersion time in the swelling step described above.

[0097] E-4. Dyeing step In the dyeing step, the PVA-based resin layer after the dry stretching step (preferably, after the swelling step) is dyed with the above-described organic dye. Specifically, a dyeing solution containing the above-described organic dye is brought into contact with the PVA-based resin layer to allow the above-described organic dye to be adsorbed.

[0098] The dyeing solution is typically an organic dye aqueous solution obtained by dissolving the above-described organic dye in water.

[0099] The content ratio of the organic dye in the dyeing solution is, for example, 0.01% by mass or more, preferably 0.05% by mass or more, and, for example, 4% by mass or less, preferably 2% by mass or less.

[0100] In one embodiment, the dyeing solution contains at least the above-described first dye. The dyeing solution preferably contains, in addition to the first dye, the above-described second dye and third dye. The content ratio of each dye can be appropriately adjusted depending on the transmittance, hue of the polarizing film desired.

[0101] The content ratio of the first dye in the dyeing solution is, for example, 0.01% by mass or more, preferably 0.05% by mass or more, and, for example, 4% by mass or less, preferably 2% by mass or less.

[0102] The content ratio of the second dye with respect to 1 part by mass of the first dye is, for example, 0.1 parts by mass or more, preferably 0.2 parts by mass or more, and, for example, 10 parts by mass or less, preferably 5 parts by mass or less.

[0103] The content ratio of the third dye with respect to 1 part by mass of the first dye is, for example, 0.1 parts by mass or more, preferably 0.2 parts by mass or more, and, for example, 10 parts by mass or less, preferably 5 parts by mass or less.

[0104] In the polarizing film (polarizing element) according to one embodiment, the combination ratio of the azo compounds used is preferably adjusted in such a manner that the transmittance becomes within the above-mentioned range. The polarizing performance of the polarizing film varies not only depending on the combination ratio of the respective azo compounds in the polarizing film, but also depending on various factors such as the swelling degree or the stretching ratio of the substrate to which the azo compounds are adsorbed, the dyeing time, the dyeing temperature, the pH at the time of dyeing, the influence of salts, and the like. The combination ratio of the respective azo compounds can be determined depending on the swelling degree of the substrate, the temperature, the time, the pH, the kind of salt, the concentration of salt, and further the stretching ratio at the time of dyeing. Note that the first dye, the second dye, and the third dye can each be used alone or in combination of two or more.

[0105] In one embodiment, the dyeing solution contains one kind of first dye, two or more kinds of second dye (preferably two kinds of second dye), and one kind of third dye.

[0106] The preferred combination of one kind of first dye, two kinds of second dye, and one kind of third dye is shown in Table 1 below.

[0107] In the dyeing process, for example, the laminate is immersed in the above-mentioned dyeing bath.

[0108] The temperature of the dyeing bath is, for example, 10°C or higher, preferably 20°C or higher, and is, for example, 80°C or lower, preferably 60°C or lower. The immersion time (dyeing time) in the dyeing process is, for example, 5 seconds or longer, preferably 30 seconds or longer, and is, for example, 300 seconds or shorter, preferably 90 seconds or shorter.

[0109] Further, the method of adsorbing the dye in the dyeing process is not limited to the above-mentioned immersion. For example, the above-mentioned dyeing solution can be applied to the PVA-based resin layer, or the above-mentioned dyeing solution can be sprayed onto the PVA-based resin layer.

[0110] E-5. Cross-linking Process In the cross-linking process, typically, the laminate after the dyeing process is immersed in a cross-linking solution (cross-linking bath). The cross-linking solution is typically an aqueous boric acid solution. The content ratio of boric acid in the cross-linking solution is, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of water.

[0111] The temperature of the cross-linking bath is, for example, 10°C or higher, preferably 20°C or higher, and is, for example, 60°C or lower, preferably 50°C or lower. The immersion time in the cross-linking process is, for example, 10 seconds or longer, preferably 20 seconds or longer, and is, for example, 200 seconds or shorter, preferably 60 seconds or shorter.

[0112] E-6. Wet Stretching Process In the wet stretching step, the PVA-based resin layer after the dyeing (preferably the PVA-based resin layer after the cross-linking step) is stretched in the long direction in a boric acid aqueous solution as a stretching bath. The wet stretching step is otherwise referred to as a water stretching step. If the PVA-based resin layer is stretched in the boric acid aqueous solution, the PVA-based resin layer can be inhibited from dissolving in the boric acid aqueous solution.

[0113] The stretching ratio in the wet stretching step is typically smaller than the stretching ratio in the dry stretching step. The stretching ratio in the wet stretching step is, for example, 3.0 times or less, preferably 2.5 times or less, more preferably 2.0 times or less, and for example, 1.3 times or more.

[0114] The product of the stretching ratio in the dry stretching step and the stretching ratio in the wet stretching step is, for example, 7.0 times or less, preferably 6.5 times or less, more preferably 5.5 times or less, further preferably 4.5 times or less, and for example, 3.5 times or more, preferably 4.0 times or more.

[0115] By stretching at the above-described stretching ratios, the thickness of the polarizing film can be stably adjusted to the above-described range, and the orientation function of the PVA-based resin in the polarizing film can be stably adjusted to the above-described range.

[0116] The content ratio of boric acid in the stretching liquid (boric acid aqueous solution) is, for example, 0.5 parts by mass or more, preferably 0.7 parts by mass or more, with respect to 100 parts by mass of water, and for example, 5 parts by mass or less, preferably 3 parts by mass or less.

[0117] The temperature of the stretching bath is, for example, 40°C or more, preferably 50°C or more, and for example, 85°C or less, preferably 80°C or less, more preferably 65°C or less. If the temperature of the stretching bath is the above-described upper limit or less, the PVA-based resin layer can be stably inhibited from dissolving in the stretching bath even if the concentration of boric acid in the stretching bath is the above-described upper limit or less. The immersion time in the stretching step is, for example, 15 seconds or more and 300 seconds or less.

[0118] E-7. Washing Step In the washing step, the laminate after the wet stretching step is typically immersed in a washing bath. The washing bath is typically water.

[0119] The temperature of the washing bath is, for example, 0°C or more, preferably 10°C or more, and for example, 40°C or less, preferably 30°C or less. The immersion time in the washing step is, for example, 5 seconds or more, preferably 10 seconds or more, and for example, 200 seconds or less, preferably 60 seconds or less.

[0120] E-8. Drying Shrinkage Step In the drying and shrinking step, the PVA-based resin layer after the wet stretching step (preferably, after the washing step) is conveyed in the long direction while being heated. The drying and shrinking step is performed by heating the drying section. The heating of the drying section can be performed by a region heating method in which the entire inside of the drying section is heated, or a heating roll drying method in which the conveying roll is heated. Both of these methods are preferably used.

[0121] The internal temperature of the heating drying section is, for example, 70°C or higher, preferably 80°C or higher, and is, for example, 120°C or lower, preferably 100°C or lower.

[0122] The surface temperature of the heating roll is, for example, 60°C or higher, preferably 70°C or higher, and is, for example, 100°C or lower, preferably 80°C or lower.

[0123] By drying using the heating roll, the heating curl of the PVA-based resin layer (laminate) can be effectively suppressed, and a polarizing film with an excellent appearance can be efficiently produced.

[0124] Further, in the drying and shrinking step, the PVA-based resin layer shrinks in the width direction orthogonal to the long direction. Thereby, the thickness of the polarizing film can be stably adjusted to the above range.

[0125] The shrinkage rate of the PVA-based resin layer in the width direction in the drying and shrinking step is, for example, 2% or higher, preferably 4% or higher. If the shrinkage rate in the width direction is equal to or higher than this lower limit, the improvement of the orientation of the PVA and the PVA / dye can be achieved, and the improvement of the polarizing properties of the polarizing film can be achieved.

[0126] The shrinkage rate of the PVA-based resin layer in the width direction is, for example, 10% or lower, preferably 8% or lower, more preferably 6% or lower. If the shrinkage rate in the width direction is equal to or lower than this upper limit, the appearance defect such as wrinkles in the polarizing film can be suppressed.

[0127] By the above steps, the polarizing film 11 can be produced.

[0128] The polarizing film described in the above items A to E can be suitably used for a polarizing plate as shown in Figure 1 and Figure 2 The polarizing plate having the above polarizing film can suppress the generation of discoloration in a humidified environment, and can suppress heat shrinkage, like the polarizing film.

[0129] F. Polarizing plate The illustrated example of the polarizing plate 10 has: the above polarizing film 11; a protective layer 12, 13 provided to at least one face of the polarizing film 11.

[0130] The protective layer is provided to at least one face of the polarizing film. In Figure 1In the polarizing plate 10 shown in FIG. 1, the protective layer 12 is provided on only one surface of the polarizing film 11. In the polarizing plate 10 shown in FIG. 2, the protective layers 12, 13 are provided on both surfaces of the polarizing film 11. The protective layers can be attached to the polarizing film via an adhesive layer, or can be attached to the polarizing film via a bonding agent layer. Figure 2 In the polarizing plate 10 shown in FIG. 1, the protective layer 12 is provided on only one surface of the polarizing film 11. In the polarizing plate 10 shown in FIG. 2, the protective layers 12, 13 are provided on both surfaces of the polarizing film 11. The protective layers can be attached to the polarizing film via an adhesive layer, or can be attached to the polarizing film via a bonding agent layer.

[0131] The protective layer is formed of any suitable film that can be used as a protective layer for a polarizing film. As specific examples of materials that are main components of the film, transparent resins such as cellulose-based resins such as triacetyl cellulose (TAC) or polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, polynorbornene-based, polyolefin-based, cycloolefin (COP)-based, (meth)acrylic-based, acetate-based resins can be listed. In addition, heat-curable resins such as (meth)acrylic-based, urethane-based, (meth)acrylic urethane-based, epoxy-based, silicone-based resins or ultraviolet-curable resins can be listed. In addition, for example, vitreous polymers such as silicone-based polymers can be listed. In addition, a polymer film described in Japanese Patent Application Publication No. 2001-343529 (WO 01 / 37007) can be used. Note that "(meth)acrylic" means acrylic and / or methacrylic.

[0132] In one embodiment, the protective layer is a phase difference film having an in-plane phase difference.

[0133] The in-plane phase difference Re(550) of the phase difference film is, for example, 100 nm to 200 nm, preferably 110 nm to 180 nm, more preferably 120 nm to 160 nm, and further preferably 130 nm to 150 nm. That is, the phase difference film can function as a so-called λ / 4 plate.

[0134] The Nz coefficient of the phase difference film is, for example, 0.9 to 2.0, preferably 0.9 to 1.5, and more preferably 0.9 to 1.2.

[0135] The phase difference film can exhibit a reverse dispersion wavelength characteristic in which the phase difference value increases in accordance with the wavelength of the measuring light, can exhibit a positive wavelength dispersion characteristic in which the phase difference value decreases in accordance with the wavelength of the measuring light, or can exhibit a flat wavelength dispersion characteristic in which the phase difference value hardly changes in accordance with the wavelength of the measuring light.

[0136] The protective layer composed of the phase difference film is typically disposed on the visible side with respect to the polarizing film 11. As the protective layer composed of the phase difference film, a COP-based film can be preferably listed.

[0137] The thickness of the protective layer is, for example, 5 mm or less, preferably 1 mm or less, more preferably 500 μm or less, further preferably 150 μm or less, particularly preferably 40 μm or less, for example, 1 μm or more, preferably 5 μm or more.

[0138] On the surface of the protective layer (the side opposite to the polarizing film), a surface treatment layer can also be provided. As the surface treatment layer, for example, a hard coat treatment layer, an anti-reflection treatment layer, an anti-blocking treatment layer, an anti-glare treatment layer can be listed. The thickness of the surface treatment layer can be arbitrarily and suitably set. The thickness of the surface treatment layer is, for example, 1 μm or more and 10 μm or less.

[0139] Further, the protective layer having an in-plane retardation can also be an orientation immobilization layer of a liquid crystal compound. Since the polarizing film is dyed by the organic dye containing the first dye, even if the protective layer is an orientation immobilization layer of a liquid crystal compound, discoloration can be sufficiently suppressed in a humidified environment (typically, relative humidity of 80% or more). Further, by using a liquid crystal compound, the difference between nxand nyof the protective layer having an in-plane retardation can be made extremely large compared to a non-liquid crystal material, and thus the thickness of the protective layer for obtaining a desired in-plane retardation can be extremely reduced. As a result, significant thinning of the polarizing plate can be achieved.

[0140] The "orientation immobilization layer" in the present specification means a layer in which a liquid crystal compound is oriented in a prescribed direction and the orientation state thereof is fixed. Note that the "orientation immobilization layer" is a concept including an orientation cured layer obtained by curing a liquid crystal monomer as described later. In the protective layer having an in-plane retardation, a rod-like liquid crystal compound is typically oriented in a state of being aligned in the slow axis direction of the protective layer (in-plane orientation).

[0141] As the liquid crystal compound, for example, a liquid crystal compound having a nematic phase (nematic liquid crystal) can be listed. As such a liquid crystal compound, for example, a liquid crystal polymer or a liquid crystal monomer can be used. The mechanism of expression of the liquid crystallinity of the liquid crystal compound can be either one of solvotropic or thermotropic. The liquid crystal polymer and the liquid crystal monomer can be used individually or in combination.

[0142] In the case where the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. By polymerizing or crosslinking (i.e., curing) the liquid crystal monomer, the orientation state of the liquid crystal monomer can be fixed. After the liquid crystal monomer is oriented, the orientation state can be fixed by, for example, polymerizing or crosslinking the liquid crystal monomers to each other. Here, a polymer is formed by polymerization and a three-dimensional network structure is formed by crosslinking, but they are non-liquid crystalline. Therefore, the protective layer having an in-plane retardation formed does not, for example, cause a transition to a liquid crystal phase, a glass phase, a crystalline phase due to a change in temperature, which is unique to a liquid crystalline compound. As a result, the protective layer having an in-plane retardation has extremely excellent stability that is not affected by a change in temperature.

[0143] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity differs depending on the kind thereof. Specifically, the temperature range is preferably 40°C to 120°C, further preferably 50°C to 100°C, and most preferably 60°C to 90°C.

[0144] As the liquid crystal monomer, any suitable liquid crystal monomer can be used. For example, a polymerizable mesogen compound described in Japanese Kokai 2002-533742 (WO 00 / 37585), EP 358208 (US 5211877), EP 66137 (US 4388453), WO 93 / 22397, EP 0261712, DE 19504224, DE 4408171, and GB 2280445, and the like can be used. As specific examples of such a polymerizable mesogen compound, for example, LC242 manufactured by BASF, E7 manufactured by Merck, and LC-Sillicon-CC 3767 manufactured by Wacker-Chem can be listed. As the liquid crystal monomer, for example, a nematic liquid crystal monomer is preferred.

[0145] The orientation-fixed layer of the liquid crystal compound can be formed by subjecting the surface of a prescribed substrate to orientation treatment, coating the surface with a coating liquid containing a liquid crystal compound, orienting the liquid crystal compound in a direction corresponding to the orientation treatment, and fixing the orientation state. In one embodiment, the substrate is any suitable resin film, and the orientation-fixed layer (protective layer) of the liquid crystal compound formed on the substrate can be transferred to the surface of the polarizing film 11 via an adhesive layer or a pressure-sensitive adhesive layer.

[0146] As the above-mentioned alignment treatment, any appropriate alignment treatment can be adopted. Specifically, a mechanical alignment treatment, a physical alignment treatment, and a chemical alignment treatment can be listed. As specific examples of the mechanical alignment treatment, rubbing treatment and stretching treatment can be listed. As specific examples of the physical alignment treatment, magnetic field alignment treatment and electric field alignment treatment can be listed. As specific examples of the chemical alignment treatment, oblique vapor deposition method and photo-alignment treatment can be listed. The treatment conditions of the various alignment treatments can be appropriately adopted depending on the purpose.

[0147] The alignment of the liquid crystal compound is performed by treating at a temperature at which a liquid crystal phase is exhibited depending on the kind of the liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes a liquid crystal state, and the liquid crystal compound is aligned in correspondence with the alignment treatment direction of the surface of the substrate.

[0148] In one embodiment, the fixation of the alignment state is performed by cooling the liquid crystal compound aligned as described above. In the case where the liquid crystal compound is a polymerizable monomer or a cross-linkable monomer, the fixation of the alignment state is performed by performing polymerization treatment or cross-linking treatment on the liquid crystal compound aligned as described above.

[0149] Specific examples of the liquid crystal compound and details of the method for forming the alignment fixation layer are described in Japanese Patent Application Publication No. 2006-163343. The description of this publication is incorporated herein by reference in its entirety.

[0150] Further, the alignment fixation layer of the liquid crystal compound can be one layer, or can be stacked by two or more layers. In the case where the alignment fixation layer of the liquid crystal compound is stacked by two or more layers, the phase difference values of the respective alignment fixation layers of the plurality of liquid crystal compounds can be different.

[0151] In the case where the protective layer is constituted by the alignment fixation layer of the liquid crystal compound, the thickness thereof is, for example, 0.5 μm to 5.0 μm, preferably 0.5 μm to 3.0 μm, and more preferably 0.5 μm to 1.5 μm.

[0152] The range of the monomer transmittance Ts of such a polarizing plate 10 is, for example, the same as the range of the monomer transmittance Ts of the above-mentioned polarizing film 11. Further, the range of the degree of polarization P of the polarizing plate 10 is, for example, the same as the range of the degree of polarization P of the above-mentioned polarizing film 11.

[0153] G. Optical Stack The polarizing film described in the above-mentioned items A to E and the polarizing plate described in the above-mentioned item F can be applied to an optical stack. The optical stack provided with the above-mentioned polarizing film can suppress the generation of discoloration in a humidified environment, and can suppress thermal shrinkage, like the polarizing film.

[0154] The polarizer 100 with a phase retardation layer shown in the figure includes: the polarizer 10 described above; a phase retardation layer 20 attached to the polarizer 10 via an adhesive layer 30; and an adhesive layer 40 located on the opposite side of the polarizer 10 relative to the phase retardation layer 20.

[0155] The retardation layer 20 is a layer having birefringence where any one of nx, ny, and nz is not equal to the others. In one embodiment, the retardation layer 20 functions as a λ / 4 plate. The retardation layer 20 can be composed of one layer or two or more layers. The retardation layer 20 preferably comprises a first retardation film whose refractive index characteristics show a relationship of nx > ny ≥ nz and a second retardation film whose refractive index characteristics show a relationship of nz > nx = ny. The first retardation film is typically composed of a stretched film of a polyester carbonate resin film. The second retardation film is typically composed of a film comprising a liquid crystal material fixed along a vertical orientation.

[0156] The angle between the absorption axis of the polarizing film 11 and the slow axis of the phase difference layer 20 is typically 40° to 50°, preferably 42° to 48°, more preferably 44° to 46°, and especially preferably 45°. With such an angle, the optical laminate can function as a circular polarizer.

[0157] When there are multiple phase retardation plates (layers), the relationship angles of their respective slow axes and the relationship angles between the polarization elements (films) and the polarization axis (absorption axis) can be appropriately set in order to obtain the desired optical performance.

[0158] Furthermore, when using an optical laminate in an IPS (in-plane switching) liquid crystal display device, a first retardation film with refractive index characteristics showing nx>ny=nz and a second retardation film with refractive index characteristics showing nz>nx=ny can be configured such that the absorption axis direction of the polarization film becomes substantially parallel to the slow axis direction of the first retardation film.

[0159] Adhesive layer 30 and adhesive layer 40 are typically composed of (meth)acrylic adhesives. The thickness of adhesive layer 30 and adhesive layer 40 is, for example, 3.5 μm or more and 35 μm or less.

[0160] like Figure 3 As shown, the phase retardation layer 20 can also be attached to the polarizer 10 via the adhesive layer 31. The adhesive layer 31 is made of any suitable adhesive. Representative examples of adhesives include UV-curable adhesives and thermosetting adhesives, and more preferably, UV-curable adhesives based on (meth)acrylic acid. The thickness of the adhesive layer 31 is, for example, 0.4 μm or more and 3.0 μm or less.

[0161] H. Image display device The polarizing film according to any one of the above-mentioned items A to E, the polarizing plate according to the above-mentioned item F, and the optical laminate according to the above-mentioned item G can be applied to an image display device. Therefore, one embodiment of the present application also includes such an image display device. As representative examples of the image display device, there can be mentioned a liquid crystal display device such as a vehicle-mounted liquid crystal display device, and an organic EL display device, and preferably a vehicle-mounted liquid crystal display device and an organic EL display device. As the vehicle-mounted liquid crystal display device, there can be mentioned a central information display for a vehicle, an instrument display for a vehicle, a mirror display, and a head-up display. The image display device of the embodiment of the present application has an image display panel including an image display unit and the polarizing film according to any one of the above-mentioned items A to E. Further, the image display device of another embodiment has an image display panel including an image display unit and the polarizing plate according to the above-mentioned item F or the optical laminate according to the above-mentioned item G. Note that the image display device is sometimes referred to as an optical display device, the image display panel is sometimes referred to as an optical display panel, and the image display unit is sometimes referred to as an optical display unit.

[0162] Further, the polarizing plate and the optical laminate including the protective layer composed of the orientation immobilization layer of the liquid crystalline compound can be thinned as compared with the case where the protective layer is composed of a resin film. The thickness of the optical laminate including the protective layer composed of the orientation immobilization layer of the liquid crystalline compound is, for example, 30 μm or less, and preferably 20 μm.

[0163] Therefore, the polarizing plate and the optical laminate including the protective layer composed of the orientation immobilization layer of the liquid crystalline compound can be applied to a foldable (folded) image display device (for example, a liquid crystal display device, an organic EL display device, and an inorganic EL display device), and particularly, can be suitably applied to a foldable (folded) organic EL display device.

[0164] I. Polarized sunglasses The polarizing film described in the above items A to E, and the polarizing plate described in the above item F can be applied to a polarized sunglass. Therefore, one embodiment of the present application also includes such a polarized sunglass. As representative examples of the polarized sunglass, depending on the transmittance, the color tone, and the degree of polarization, there are driving use, sports use, and leisure use, and also including a wraparound type, a type with a prescribed power. The polarized sunglass of the embodiment of the present application is provided with a lens including the polarizing film described in the above items A to E, and a frame made of resin or metal. Further, the polarized sunglass of another embodiment is provided with a lens including the polarizing plate described in the above item F, and a frame made of resin or metal. The lens is typically made of glass, polycarbonate-based resin, or polyamide-based resin as a raw material. The polarizing film or the polarizing plate is generally laminated on the lens raw material by adhesion or fusion of a protective layer of the polarizing film and the lens raw material, to become a polarized lens. The polarized lens is appropriately provided with a hard coat layer, an anti-reflection film, or the like on its surface, and then fixed to the frame by rounding, hole formation, screw fastening, or the like, to become a polarized sunglass. Note that the polarized sunglass is sometimes referred to as a polarized eyeglass, a polarized sunglass, or a polarized eyeglass.

[0165] Example Hereinafter, the present application will be specifically described by way of examples, but the present application is not limited by these examples. The measuring method of each property is as follows.

[0166] (1) Thickness measurement A film thickness tester (HKT-1202, manufactured by Fujiwork) was used to measure the thickness of the polarizing film obtained in the examples and comparative examples. The results are shown in Tables 2 and 3.

[0167] (2) Measurement of crystallization index In the examples and comparative examples, the crystallization index of the PVA-based resin layer (before wet stretching) was measured by attenuated total reflection (ATR) measurement using a Fourier transform infrared spectrophotometer. Specifically, polarized light was used as the measuring light, and based on the obtained spectrum, the area ratio of the second peak to the first peak (second peak / first peak) was calculated as the crystallization index of the PVA-based resin. The results are shown in Tables 2 and 3. -1 The area ratio of the second peak to the first peak (second peak / first peak) was calculated as the crystallization index of the PVA-based resin. The results are shown in Tables 2 and 3. -1 The area ratio of the second peak to the first peak (second peak / first peak) was calculated as the crystallization index of the PVA-based resin. The results are shown in Tables 2 and 3.

[0168] (3) Measurement of orientation function In the examples and comparative examples, for the PVA-based resin layer (before wet stretching) and the polarizing film, a Fourier transform infrared spectrophotometer (FT-IR) (Perkin Elmer, trade name: "Frontier") was used to measure the ATR of their surfaces (specifically, the surface opposite to the resin substrate in the PVA-based resin layer, or the peeled surface of the resin substrate in the polarizing film) using polarized infrared light as the measurement light. Germanium was used as the microcrystal, and the incident angle of the measurement light was set to 45°. The orientation function was calculated using the following steps: The incident polarized infrared light (measurement light) was set to be polarized light (s-polarized light) vibrating parallel to the plane that held the germanium crystal sample together. The absorbance spectra were measured with the polarizing film positioned perpendicular (⊥) and parallel ( / / ) to the stretching direction relative to the polarization direction of the measurement light. From the obtained absorbance spectra, the ATR of the polarizing film was calculated at (3330 cm⁻¹). -1 (Strength) as a reference (2941cm) -1 Intensity) I. I⊥ is obtained from the absorbance spectrum (2941 cm⁻¹) when the polarizing film is arranged perpendicular (⊥) to the stretching direction of the polarizing film relative to the polarization direction of the measurement light. -1 Strength) / (3330cm) -1 Intensity). Furthermore, I / / was obtained from the absorbance spectrum (2941 cm⁻¹) when the stretching direction was arranged parallel to the polarization direction of the measurement light ( / / ). -1 Strength) / (3330cm) -1 Strength). Here, (2941cm) -1 Intensity) is the bottom of the absorbance spectrum, i.e., at 2770 cm⁻¹. -1 and 2990cm -1 2941cm as the baseline -1 absorbance (3330cm) -1 Strength) is based on 2990cm -1 and 3650cm -1 3330cm as the baseline -1 The absorbance. Using the obtained I⊥ and I / / , the orientation function f is calculated according to the following formula (1). The results are shown in Tables 2 and 3.

[0169] f = (3) <cos 2 θ>-1) / 2=(1-D) / [c(2D+1)]…(1) in, In c = (3cos 2 β-1) / 2, and use 2941cm as described above. -1 In the case of β=90°=>f=-2×(1-D) / (2D+1).

[0170] θ: angle of the molecular chain with respect to the stretching direction β: angle of the transition dipole moment with respect to the molecular chain axis D = (I⊥) / (I / / ) I⊥: absorption intensity in the case where the polarization direction of the measuring light is perpendicular to the stretching direction I / / : absorption intensity in the case where the polarization direction of the measuring light is parallel to the stretching direction Note that f = 1 becomes complete orientation, and f = 0 becomes random. In addition, the peak at 2941 cm -1 is said to be absorption due to vibration of the main chain (-CH2-) of the PVA-based resin. In addition, the peak at 3330 cm -1 is said to be absorption due to vibration of the hydroxyl group of the PVA-based resin.

[0171] (4) Puncture strength test The polarizing film obtained in the examples and comparative examples was peeled from the resin substrate, placed in a compression testing machine (manufactured by KATO TECH Co., Ltd., product name "NDG5" needle penetration force measuring gauge) equipped with a needle, and punctured at a puncture speed of 0.33 cm / sec in a room temperature (23°C ± 3°C) environment, and the strength at which the polarizing film cracked was taken as the puncture strength (breaking strength). As for the evaluation value, the puncture strength (breaking strength) of 10 test pieces was measured, and the average value thereof was used. Note that a needle having a front end diameter of 1 mmφ, 0.5R was used. The measured polarizing film was clamped and fixed from both sides of the polarizing film using a jig having a circular opening portion with a diameter of about 11 mm, and the needle was punctured in the center of the opening portion to perform the test. The results thereof are shown in Tables 2 and 3.

[0172] (5) Measurement of monomer transmittance and degree of polarization An ultraviolet-visible spectrophotometer (manufactured by Shimadzu Corporation, product name "V7100") was used to measure the monomer transmittance (Ts: initial transmittance), parallel transmittance (Tp), and orthogonal transmittance (Tc) of the polarizing sheet obtained in the examples and comparative examples. Further, the degree of polarization (P) of the polarizing sheet was calculated by the following formula (1).

[0173] Degree of polarization (P) (%) = { (Tp - Tc) / (Tp + Tc)}1 / 2x 100... (1) Note that the above Ts, Tp, and Tc are Y values measured by a 2-degree field (C light source) of JIS Z8701, and visibility correction was performed.

[0174] (6) Measurement of reflectance The optical laminate obtained in each of Examples and Comparative Examples was disposed on an aluminum reflector. Thereafter, using a spectrophotometer ("CM-2600d" manufactured by KONICA MINOLTA Co., Ltd.), light was irradiated from the polarizing plate side, and the reflectance of the optical laminate (initial reflectance) was measured in an SCI mode. The results are shown in Tables 2 and 3.

[0175] (7) High humidity durability test (end discoloration) After the optical laminate obtained in each of Examples and Comparative Examples was attached to a glass, it was left to stand in an environment of 65°C, 90% RH (relative humidity) for 120 hours. Thereafter, using an optical microscope, it was observed whether or not discoloration occurred from the end portion of the polarizing film in the direction of the two end portions of the absorption axis direction of the polarizing film. The results are shown in Tables 2 and 3. Further, the dimensional shrinkage ratio of the stretching direction (MD direction) of the polarizing film in the high humidity durability test was measured by the following method. The obtained optical laminate was cut into a square of 10 cm in the absorption axis direction x 10 cm in the transmission axis direction, and used as a test sample. The precise dimensions of the test sample in the absorption axis direction and the transmission axis direction were measured with a "CNC image measuring device" manufactured by Mitutoyo Co., Ltd., and the dimension in the absorption axis direction (MD direction) was set as S MD0 . After the dimension measurement, the test sample was left to stand in 65°C, 90% RH for 120 hours, and similarly, the dimension after the test was measured. The dimension in the MD direction after the test was set as S MD1 . The shrinkage ratio S MD in the absorption axis direction was calculated by (S MD1 -S MD0 ) / S MD0 x 100. The results are shown in Table 2.

[0176] Further, the single transmission (Ts) of the polarizing plate after the high humidity durability test was measured in the same manner as in the above "(5) Measurement of single transmission and degree of polarization", and ΔTs of the polarizing plate ((transmission after the high humidity durability test) - (transmission before the high humidity durability test)) was calculated. The results are shown in Tables 2 and 3.

[0177] (8) Heat shrinkage test After the optical laminate obtained in each of Examples and Comparative Examples was attached to a glass, it was left to stand in an environment of 80°C for 120 hours. At this time, it was observed whether or not a crack was generated in the optical laminate. The results are shown in Table 2. Thereafter, in the same manner as in the measurement of the dimensional shrinkage in the high humidity durability test (7), the dimensional shrinkage ratio of the stretching direction (MD direction) of the polarizing film in the heat shrinkage test was measured. The results are shown in Tables 2 and 3.

[0178] (9) Humidity heat durability test After the optical laminate obtained in the Examples and Comparative Examples was attached to a glass, it was left to stand in an environment of 85°C, 85% RH (relative humidity) for 500 hours. After that, the monomer transmittance (Ts) of the polarizing plate after the heat-humidity durability test was measured in the same manner as in the above "(5) Measurement of monomer transmittance and degree of polarization", and ΔTs of the polarizing plate ((transmittance after the durability test) - (transmittance before the durability test)) was calculated. The results are shown in Table 2.

[0179] (10) High-temperature durability test After the optical laminate obtained in the Examples and Comparative Examples was attached to a glass, it was left to stand in an environment of 105°C for 1000 hours. After that, the monomer transmittance (Ts) of the polarizing plate after the high-temperature durability test was measured in the same manner as in the above "(5) Measurement of monomer transmittance and degree of polarization", and ΔTs of the polarizing plate was calculated. The results are shown in Table 2.

[0180] <<Manufacturing Example 1>> <1st phase difference film> Into a batch polymerization device including 2 vertical reactors equipped with stirring blades and a reflux cooler controlled to 100°C, bis[9-(2-phenoxy carbonyl ethyl) fluorene-9-yl]methane 29.60 parts by mass (0.046 mol), isosorbide (ISB) 29.21 parts by mass (0.200 mol), spiro glycol (SPG) 42.28 parts by mass (0.139 mol), diphenyl carbonate (DPC) 63.77 parts by mass (0.298 mol), and calcium acetate monohydrate 1.19 x 10 -2 parts by mass (6.78 x 10 - 5 mol) as a catalyst were charged. After the inside of the reactor was replaced with nitrogen under reduced pressure, the reactor was warmed with a heating medium, and stirring was started when the inside temperature reached 100°C. The inside temperature reached 220°C 40 minutes after the start of the temperature increase, and the temperature was controlled so as to be maintained at this temperature, and at the same time, the pressure was reduced. Phenol vapor produced as a byproduct of the polymerization reaction was introduced into a reflux cooler at 100°C, and a certain amount of monomer components contained in the phenol vapor was returned to the reactor, and the uncondensed phenol vapor was introduced into a condenser at 45°C and recovered. The oligomerized reaction solution in the 1st reactor was transferred to the 2nd reactor after the pressure was temporarily returned to atmospheric pressure by introducing nitrogen into the 1st reactor. Then, the temperature increase and the pressure reduction in the 2nd reactor were started, and the inside temperature was set to 240°C and the pressure was set to 0.2 kPa over 50 minutes. After that, the polymerization was performed until the prescribed stirring power was obtained. The pressure was returned by introducing nitrogen into the reactor when the prescribed power was obtained, and the polyester carbonate resin produced was extruded into water, and the strands were cut to obtain pellets.

[0181] After vacuum drying the obtained polyester carbonate-based resin (pellets) at 80°C for 5 hours, a film was produced using a film production apparatus equipped with a single-screw extruder (Toshiba Machine Co., Ltd., barrel set temperature: 250°C), a T die (width 200 mm, set temperature: 250°C), a chill roll (set temperature: 120 to 130°C), and a winder, to produce a long resin film having a thickness of 125 μm. The obtained long resin film was subjected to free-end longitudinal stretching at 140°C to 2.5 times to obtain a first phase difference film (positive A plate) having a thickness of 50 μm. The refractive index characteristics of the second phase difference film showed a relationship of nx>ny=nz.

[0182] <Second phase difference film> A liquid crystal coating liquid was prepared by dissolving 20 parts by mass of a side chain type liquid crystal polymer represented by the following formula (I) (the numbers 65 and 35 in the formula represent the mole% of monomer units; for convenience, a block polymer is represented: weight average molecular weight 5000), 80 parts by mass of a polymerizable liquid crystal (BASF Co., Ltd.: trade name Paliocolor LC242) showing a nematic liquid crystal phase, and 5 parts by mass of a photopolymerization initiator (IGM Resins B.V. Co., Ltd., trade name Omnirad 907) in 200 parts by mass of cyclopentanone.

[0183] [Chemical Formula 5] Then, the coating liquid was coated on a base film (norbornene-based resin film: ZEON CORPORATION, trade name "ZEONEX") using a bar coater, and the liquid crystal was oriented by heating and drying at 80°C for 4 minutes. The liquid crystal layer was cured by irradiating the liquid crystal layer with ultraviolet rays, thereby forming a second phase difference film (positive C plate) having a thickness of 2 μm on the base. The refractive index characteristics of the second phase difference film showed a relationship of nz>nx=ny.

[0184] <λ / 4 plate> Next, the first phase difference film (positive A plate) and the second phase difference film (positive C plate) were adhered by a UV-curable adhesive (thickness 1 μm) to obtain a λ / 4 plate.

[0185] <<Manufacturing Example 2>> A liquid crystal composition (coating liquid) was prepared by dissolving 10 parts by mass of a polymerizable liquid crystal (BASF Co., Ltd.: trade name "Paliocolor LC242") showing a nematic liquid crystal phase and 3 parts by mass of a photopolymerization initiator (IGM Resins B.V. Co., Ltd., trade name Omnirad 907) for the polymerizable liquid crystal compound in 40 parts by mass of toluene.

[0186] A polyethylene terephthalate (PET) film (thickness: 38 μm) was rubbed with a rubbing cloth to perform orientation treatment. The orientation treatment was performed so that the direction of the rubbed surface would be 45° with respect to the direction of the absorption axis of a polarizer when viewed from the visual side when the polarizing plate was attached to the polarizer. The above liquid crystal coating solution was applied to the surface subjected to the orientation treatment by a bar coater, and the liquid crystal compound was oriented by heating and drying at 90°C for 2 minutes. The liquid crystal layer formed by the above operation was cured by irradiation of 1 mJ / cm2of light from a metal halide lamp, thereby forming an orientation-fixed layer of the liquid crystal compound on the PET film. The thickness of the orientation-fixed layer of the liquid crystal compound was 1 μm. The orientation-fixed layer of the liquid crystal compound had a refractive index characteristic of nx>ny=nz, and an in-plane retardation Re(550) of 140 nm. 2

[0187] <<Examples 1 to 3>> As the thermoplastic resin substrate, a long strip-shaped, amorphous copolymerized polyethylene terephthalate film of isophthalic acid (thickness: 100 μm) having a Tg of about 75°C was used, and a single surface of the resin substrate was subjected to corona treatment.

[0188] A PVA aqueous solution (coating solution) was prepared by adding 12 parts by mass of potassium iodide to 100 parts by mass of a PVA-based resin prepared by mixing polyvinyl alcohol (degree of polymerization: 4200, degree of saponification: 99.2 mol%) and acetyl acetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") at a ratio of 9:1, and dissolving the mixture in water.

[0189] A PVA-based resin layer having a thickness of 13 μm was formed by applying the above PVA aqueous solution to the corona-treated surface of the resin substrate and drying at 60°C, and a laminate was prepared.

[0190] Next, the laminate was uniaxially stretched (dry stretching step) in the longitudinal direction (lengthwise direction) at the dry stretching ratio shown in Table 2 in an oven at 130°C. The PVA-based resin layer after the uniaxial stretching was subjected to the above "(2) Measurement of crystallization index" and "(3) Measurement of orientation function".

[0191] Subsequently, the laminate was immersed in a swelling bath (pure water) at a liquid temperature of 40°C for 60 seconds (swelling step).

[0192] ​Next, the laminate was immersed in a dyeing bath at a liquid temperature of 52°C for 60 seconds (dyeing step). The dyeing bath was prepared by dissolving the combination example 1, i.e., the first dye (compound example 140), the second dye A (compound example 269), the second dye B (compound example 396), and the third dye (compound example 454) in water. In the dyeing bath, the concentration of the first dye was 0.18 mass%, the concentration of the second dye A was 0.09 mass%, the concentration of the second dye B was 0.11 mass%, and the concentration of the third dye was 0.11 mass%.

[0193] After that, the laminate was uniaxially stretched in the longitudinal direction (lengthwise direction) at the wet stretching ratio shown in Table 2 while being immersed in a stretching bath (boric acid aqueous solution obtained by mixing 4 parts by mass of boric acid with respect to 100 parts by mass of water) at a liquid temperature of 60°C and passing between rollers having different circumferential speeds (wet stretching step). In addition, the total stretching ratio of the dry stretching step and the wet stretching step is shown in Table 2.

[0194] Next, the laminate was immersed in a washing bath (water) at a liquid temperature of 20°C (washing treatment).

[0195] After that, the laminate was dried while being kept in an oven at about 90°C and was brought into contact with a heating roller made of SUS whose surface temperature was kept at about 75°C (drying shrinkage step). Thus, the PVA-based resin layer on the resin substrate was shrunk in the width direction, and a polarizing film was formed. The thickness of the polarizing film is shown in Table 2. In addition, the obtained polarizing film was subjected to the above-described "(3) Measurement of Orientation Function" and "(4) Puncture Strength Test".

[0196] Next, a cycloolefin (COP)-based film (ZEON CORPORATION, ZD+, thickness 27 μm) was attached to the surface of the polarizing film (the side opposite to the resin substrate) via an ultraviolet-curable adhesive layer (thickness 1 μm) as a protective layer. The COP-based film had an in-plane retardation, and Re(550) was 137.5 nm. That is, the COP-based film was a phase difference film that can function as a λ / 4 plate. In addition, a hard coat layer having a thickness of 2 μm was provided on the surface of the COP-based film opposite to the polarizing film.

[0197] Next, the resin substrate was peeled off, and a polarizing plate having a configuration of a protective layer / polarizing film was obtained. The obtained polarizing plate was subjected to the above-described "(5) Measurement of Monomer Transmittance and Degree of Polarization".

[0198] Next, the λ / 4 plate of Production Example 1 was attached to the peeling surface of the resin substrate (the side opposite to the protective layer) in the polarizing film via a (meth)acrylic-based adhesive layer (thickness 5 μm). After that, a (meth)acrylic-based adhesive layer (thickness 15 μm) was formed on the λ / 4 plate.

[0199] Thus, an optical laminate having a constitution of a protective layer / (meth)acrylic adhesive layer / 1st phase difference film / 2nd phase difference film / (meth)acrylic adhesive layer was obtained.

[0200] The obtained optical laminate was subjected to the above-mentioned "(6) Measurement of reflectance", "(7) High humidity durability test (end portion discoloration)", "(8) Heat shrinkage test", "(9) Humidity heat durability test", and "(10) High temperature durability test".

[0201] <<Example 4>> A polarizing film was prepared in the same manner as in Example 3.

[0202] Next, the COP-based film (ZEON CORPORATION, ZD+, thickness 27 μm) was attached to the surface of the polarizing film (the side opposite to the resin substrate) via a UV-curable adhesive layer (thickness 1 μm) as a protective layer. Next, the resin substrate was peeled off, and a triacetyl cellulose (TAC) film (KONICA MINOLTA, KC-2CT, thickness 20 μm) was attached to the peeled surface of the resin substrate in the polarizing film via a UV-curable adhesive layer (thickness 1 μm) as a protective layer.

[0203] Thus, a polarizing plate having a constitution of a protective layer (COP-based film) / polarizing film / protective layer (TAC film) was obtained.

[0204] Next, the λ / 4 plate of Production Example 1 was attached to the surface of the TAC film via a (meth)acrylic adhesive layer (thickness 15 μm). Thereafter, a (meth)acrylic adhesive layer (thickness 23 μm) was formed on the λ / 4 plate.

[0205] Thus, an optical laminate having a constitution of a protective layer / polarizing film / protective layer / (meth)acrylic adhesive layer / 1st phase difference film / 2nd phase difference film / (meth)acrylic adhesive layer was obtained. The obtained polarizing plate and optical laminate were subjected to each measurement and test in the same manner as in Example 1.

[0206] <<Example 5>> A polarizing film was prepared in the same manner as in Example 2.

[0207] Next, the orientation immobilization layer of the liquid crystal compound prepared in Production Example 2 was attached to the surface of the polarizing film (the side opposite to the resin substrate) via a UV-curable adhesive layer (thickness 1 μm) as a protective layer. Next, the resin substrate was peeled off, and a polarizing plate having a constitution of an orientation immobilization layer of a liquid crystal compound / polarizing film was obtained. The obtained polarizing plate was subjected to the above-mentioned "(5) Measurement of monomer transmittance and degree of polarization".

[0208] Next, the λ / 4 plate of Production Example 1 was attached to the peeling surface of the resin substrate in the polarizing film (the surface opposite to the protective layer) via a UV-curable adhesive layer (thickness 1 μm). Thereafter, a (meth)acrylic adhesive layer (thickness 5 μm) was formed on the λ / 4 plate.

[0209] Thus, an optical laminate having a constitution of an orientation immobilization layer of a liquid crystalline compound / polarizing film / first phase difference film / second phase difference film / (meth)acrylic adhesive layer was obtained.

[0210] The obtained optical laminate was subjected to the above-mentioned "(6) Measurement of reflectance", "(7) High humidity durability test (end discoloration)", and "(8) Heat shrinkage test".

[0211] <<Comparative Example 1>> An optical laminate was obtained in the same manner as in Example 4 except that the first dye was changed to the azo compound of formula (4) described in Japanese Patent No. 5296536. The obtained optical laminate was subjected to each measurement and test in the same manner as in Example 1.

[0212] <<Comparative Example 2>> Instead of the organic dyes (the first dye, the second dye, and the third dye), an iodine and potassium iodide dyeing bath was prepared by dissolving iodine and potassium iodide in water, and an optical laminate was obtained in the same manner as in Comparative Example 1 except for this. The mass ratio of iodine to potassium iodide in the dyeing bath was 1:7, and the iodine concentration in the dyeing bath was 0.2 mass%. The obtained optical laminate was subjected to each measurement and test in the same manner as in Example 1.

[0213] <<Comparative Example 3>> A polyvinyl alcohol (PVA)-based film (Kuraray Co., Ltd., PE3000) having a thickness of 30 μm was stretched to 2 times while being treated with pure water at 20°C (swelling step).

[0214] Next, the PVA-based film was dyed by uniaxially stretching to a stretch ratio of 2.4 times with respect to the original length while being immersed in a dyeing bath at a liquid temperature of 30°C for 60 seconds (dyeing step). As the dyeing bath, an iodine dyeing solution having a concentration of 0.7 mass% of iodine:potassium iodide (mass ratio = 1:7) was used.

[0215] Next, the PVA-based resin film after the dyeing step was crosslinked by uniaxially stretching to a total stretch ratio of 3 times with respect to the original length while being immersed in a crosslinking bath (boric acid aqueous solution obtained by mixing 5 parts by mass of boric acid and 3 parts by mass of potassium iodide with respect to 100 parts by mass of water) at a liquid temperature of 40°C for 45 seconds (crosslinking step).

[0216] Next, the PVA-based resin film after the cross-linking step was immersed in a stretching bath (boric acid aqueous solution obtained by mixing 4 parts by mass of boric acid and 5 parts by mass of potassium iodide with respect to 100 parts by mass of water) at a liquid temperature of 60°C for 30 seconds while being uniaxially stretched to a total stretch ratio of 6 times with respect to the original length (stretching step).

[0217] Next, the PVA-based resin film after the stretching step was immersed in a washing bath (potassium iodide aqueous solution) at a liquid temperature of 20°C (washing treatment).

[0218] After that, the PVA-based resin film after the washing step was dried in an oven at 60°C for 4 minutes to obtain a polarizing film having a thickness of 12 μm. The obtained polarizing film was used for each measurement and test in the same manner as in Example 1.

[0219] Next, the COP-based film (ZEON CORPORATION, ZD+, thickness 27 μm) described above was attached to one face of the obtained polarizing film as a protective layer via a water-based adhesive layer. Next, the TAC film (KONICA MINOLTA, KC-2CT, thickness 20 μm) described above was attached to the other face of the polarizing film as a protective layer via a water-based adhesive layer.

[0220] Thus, a polarizing plate having a configuration of protective layer (COP-based film) / polarizing film / protective layer (TAC film) was obtained.

[0221] Next, the λ / 4 plate of Production Example 1 was attached to the surface of the TAC film via a (meth)acrylic-based adhesive layer (thickness 15 μm). After that, a (meth)acrylic-based adhesive layer (thickness 23 μm) was formed on the λ / 4 plate.

[0222] Thus, an optical laminate having a configuration of protective layer / polarizing film / protective layer / (meth)acrylic-based adhesive layer / first phase difference film / second phase difference film / (meth)acrylic-based adhesive layer was obtained. The obtained polarizing plate and optical laminate were used for each measurement and test in the same manner as in Example 1.

[0223] <<Comparative Example 4>> A polarizing film was produced in the same manner as in Comparative Example 2, and an optical laminate was obtained by using it and operating in the same manner as in Example 3. The obtained polarizing plate and optical laminate were used for each measurement and test in the same manner as in Example 1.

[0224] <<Comparative Example 5>> Instead of organic dyes (dye 1, dye 2, and dye 3), a dyeing bath was prepared by dissolving iodine and potassium iodide in water. Otherwise, the optical laminate was obtained by operating in the same manner as in Example 5. The mass ratio of iodine to potassium iodide in the dyeing bath was 1:7, and the iodine concentration in the dyeing bath was 0.2% by mass. The obtained optical laminate was subjected to various measurements and tests in the same manner as in Example 5.

[0225] <<Comparative Example 6>> Instead of organic dyes (dye 1, dye 2 and dye 3), iodine and potassium iodide were dissolved in water to prepare a dyeing bath. Otherwise, the polarizing film was prepared in the same manner as in Example 3.

[0226] Next, an alignment layer of the liquid crystal compound prepared in Manufacturing Example 2 was attached as a protective layer to the surface of the polarizing film (the side opposite to the resin substrate) through a UV-curable adhesive layer (1 μm thick). Then, the resin substrate was peeled off to obtain a polarizer having the alignment layer / polarizing film of the liquid crystal compound. The obtained polarizer was then subjected to the above-described "(5) Measurement of monomer transmittance and polarization".

[0227] Next, the λ / 4 plate of Manufacturing Example 1 is attached to the release surface (the side opposite to the protective layer) of the resin substrate in the polarizing film via a UV-curable adhesive layer (1 μm thick). Afterward, a (meth)acrylic adhesive layer (5 μm thick) is formed on the λ / 4 plate.

[0228] Thus, an optical laminate consisting of an orientation immobilization layer of liquid crystal compound, a polarizing film, a first phase reversal film, a second phase reversal film, and a (meth)acrylic adhesive layer is obtained.

[0229] The obtained optical laminate was subjected to the above-mentioned "(6) Measurement of reflectivity", "(7) High humidity durability test (end decolorization)" and "(8) Heat shrinkage test".

[0230] [evaluate] As shown in Tables 2 and 3, it was found that for optical laminates (Examples 1-5) having a polarizing film containing the first dye shown in Formula (1) and having a thickness of 10 μm or less, decolorization and thermal shrinkage under humidified conditions were suppressed, ensuring excellent optical properties. In particular, it was found that if the orientation function of the PVA-based resin contained in the polarizing film is 0.30 or less (Examples 1 and 2), thermal shrinkage is significantly suppressed in polarizing films containing organic dyes.

[0231] Further, the optical laminate including the polarizing film containing the first dye (Examples 1 to 5) was excellent in various durability compared with the optical laminate including the polarizing film containing iodine (Comparative Examples 2 to 6).

[0232] Industrial applicability The polarizing film of the present application is suitably used for image display devices (typically, liquid crystal display devices, organic EL display devices), polarizing sunglasses. In the image display devices, more preferably, it can be used for in-vehicle liquid crystal display devices such as central information display, instrument display, mirror display, head-up display, etc. which require stable display in a severe environment.

[0233] Explanation of symbols 10 polarizing plate 11 polarizing film 12 protective layer 100 optical laminate

Claims

1. A polarizing film which is a polarizing film of 10 μm or less comprising a polyvinyl alcohol-based resin, the polarizing film comprising at least a first dye which is an azo compound or a salt thereof having a urea skeleton represented by the following formula (1): in the formula (1), Ay1 and Ay2 are each independently a naphthyl group which can have a substituent, or a phenyl group which can have a substituent, s and t are each independently 0 or 1, and either one of s or t is 1, and Ry1 to Ry8 each independently represent a hydrogen atom or a substituent: the phenyl group which can have a substituent refers to a phenyl group having at least one or more substituents selected from the group consisting of a sulfo group, a carboxyl group, an alkyl group having a sulfo group with a carbon number of 1 to 4, an alkyl group with a carbon number of 1 to 4, an alkoxy group with a carbon number of 1 to 4, a halogen atom, a nitro group, an amino group, an alkyl group-substituted amino group with a carbon number of 1 to 4, and an alkyl group-substituted acylamino group with a carbon number of 1 to 4, and the naphthyl group which can have a substituent refers to a naphthyl group which can have a substituent selected from the group consisting of a hydroxyl group, an alkoxy group having a sulfo group with a carbon number of 1 to 4, and a sulfo group: Ry1, Ry2, Ry7, and Ry8 are each independently a hydrogen atom, an alkyl group with a carbon number of 1 to 4, or an alkoxy group with a carbon number of 1 to 4, and Ry3 to Ry6 are each independently a hydrogen atom, an alkyl group with a carbon number of 1 to 4, an alkoxy group with a carbon number of 1 to 4, or an alkoxy group having a sulfo group with a carbon number of 1 to 4.

2. The polarizing film according to claim 1, wherein an orientation function of the polyvinyl alcohol-based resin is 0.30 or less.

3. The polarizing film according to claim 1, further comprising a second dye which is an azo compound or a salt thereof represented by the following formula (2) and a third dye which is an azo compound or a salt thereof represented by the following formula (3): In formula (2), Ar 11 represents a phenyl group having a substituent, or a naphthyl group having a substituent, Rr 11 ~Rr 16 each independently represents a hydrogen atom, an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 and having a sulfo group, Xr 11 represents an amino group which can have a substituent selected from the group consisting of an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, a benzoyl group which can have a substituent selected from the group consisting of an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, a phenylamino group which can have a substituent selected from the group consisting of an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, a benzoylamino group which can have a substituent selected from the group consisting of an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, a phenylazo group which can have a substituent selected from the group consisting of an alkoxy group having a carbon number of 1 to 4, a sulfo group, a hydroxyl group, an amino group, and a substituted amino group, or a naphthotriazolyl group which can have a substituent selected from the group consisting of an alkyl group having a carbon number of 1 to 4, an alkoxy group having a carbon number of 1 to 4, a sulfo group, an amino group, and a substituted amino group, m1 and n1 each independently represent 0 or 1, in the case where m1 and n1 are 1, Rr 15 and Rr 16 each independently represents a hydrogen atom, an alkyl group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4, in the case where m1 and n1 are 0, Rr 11 and Rr 12 each independently represents a hydrogen atom, an alkyl group having a carbon number of 1 to 4, or an alkoxy group having a carbon number of 1 to 4 and having a sulfo group. In formula (3), A is the same as Ar of the formula (2) 11 Also, or a substituent represented by the following general formula (4), in the formula (4), A1 represents a nitro group or an amino group, R1~R4, R6and Rr of the formula (2) 11 Rr 14 Also, X and Xr of the formula (2) 11 Also, m and n are each 0 or 1.

4. A vehicle-mounted liquid crystal display device provided with the polarizing film according to any one of claims 1 to 3.

5. An image display device provided with the polarizing film according to any one of claims 1 to 3.

6. Polarized sunglasses provided with the polarizing film according to any one of claims 1 to 3.

7. A method for producing a polarizing film, comprising the following steps in this order: a laminate production step of applying a coating liquid containing a polyvinyl alcohol-based resin to a long strip-shaped thermoplastic resin substrate to produce a laminate provided with a polyvinyl alcohol-based resin layer and the thermoplastic resin substrate; a dry stretching step of aerially stretching the laminate; a dyeing step of dyeing the polyvinyl alcohol-based resin layer after the dry stretching step with at least a first dye which is an azo compound or a salt thereof having a urea skeleton represented by the following formula (1); a wet stretching step of stretching the polyvinyl alcohol-based resin layer after the dyeing step in a stretching bath; and a dry shrinkage step of adjusting the thickness to 10 μm or less by conveying the polyvinyl alcohol-based resin layer after the wet stretching step in a long strip direction while causing it to shrink in a width direction orthogonal to the long strip direction. In formula (1), Ay1and Ay2are each independently a naphthyl group which can have a substituent, or a phenyl group which can have a substituent, s and t are each independently 0 or 1, and either one of s or t is 1, Ry1to Ry8each independently represent a hydrogen atom or a substituent: the phenyl group which can have a substituent refers to a phenyl group having at least one or more substituents selected from the group consisting of a sulfo group, a carboxyl group, an alkoxy group having a sulfo group with a carbon number of 1 to 4, an alkyl group with a carbon number of 1 to 4, an alkoxy group with a carbon number of 1 to 4, a halogen atom, a nitro group, an amino group, an alkyl-substituted amino group with a carbon number of 1 to 4, and an alkyl-substituted acylamino group with a carbon number of 1 to 4, the naphthyl group which can have a substituent refers to a naphthyl group which can have a substituent selected from the group consisting of a hydroxyl group, an alkoxy group having a sulfo group with a carbon number of 1 to 4, and a sulfo group: Ry1, Ry2, Ry7, and Ry8are each independently a hydrogen atom, an alkyl group with a carbon number of 1 to 4, or an alkoxy group with a carbon number of 1 to 4, and Ry3to Ry6are each independently a hydrogen atom, an alkyl group with a carbon number of 1 to 4, an alkoxy group with a carbon number of 1 to 4, or an alkoxy group having a sulfo group with a carbon number of 1 to 4.

8. The method of producing a polarizing film according to claim 7, wherein The stretching ratio in the dry stretching is 2.1 times or more, The stretching ratio in the wet stretching is 2.0 times or less.

Citation Information

Patent Citations

  • Liq. crystalline (LC) material

    DE19504224A1

  • Novel polymerizable liquid crystalline compounds

    DE4408171A1

  • Liquid crystalline reticulated polysiloxanes

    EP0066137A1

  • Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer

    EP0261712A1

  • Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups

    EP0358208A2